Long strip film

By setting up an uneven structure at the end of the short side of the base film of the long film and stacking functional layers on it, the problem that the liquid crystal cured material layer is difficult to peel off linearly during the transfer process, and the alignment of the functional layers is achieved Peel and efficient transfer.

CN114051586BActive Publication Date: 2025-02-07SUMITOMO CHEM CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202080047996.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-11
Filing Date
2020-06-26
Publication Date
2025-02-07
Estimated Expiration
2040-06-26

AI Technical Summary

Technical Problem

During the transfer process, the short-side end of the optical film containing the liquid crystal cured product layer is difficult to peel off linearly, resulting in tearing and detachment of the functional layer.

Method used

A long film has been designed, and the base film has an uneven structure at the end of the short side direction, and the functional layer containing polymerizable liquid crystal compound is laminated on the uneven surface of the base film to ensure that the substrate film is peeled off. The functional layer can be peeled off in a straight line along the concave and convex portions.

Benefits of technology

By providing concave and convex portions at the end of the base film, the adhesion between the functional layer and the base film is improved, ensuring that the functional layer is not easily disengaged during the peeling process, and the transfer efficiency and yield rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114051586B_ABST
    Figure CN114051586B_ABST
Patent Text Reader

Abstract

The present invention provides a long film having a substrate film and a functional layer including a transferable liquid crystal cured layer, wherein the functional layer at the end of the short side direction is not easily detached when the substrate film is peeled off, and an optical film with excellent optical properties can be manufactured with good productivity. The long film comprises: a long substrate film having a concave-convex portion at at least one end of the short side direction of at least one side; and a transferable functional layer, which comprises a cured layer of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound, wherein the functional layer is laminated on the surface of the substrate film having the concave-convex portion, and when the total width of the substrate film in the short side direction is set to A, the total width of the concave-convex portion of the substrate film in the short side direction is set to B, and the width of the functional layer in the short side direction is set to C, B+C>A is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a long film, and more particularly to a long film comprising a substrate film and a functional layer including a liquid crystal cured material layer. Background Art

[0002] An elliptically polarizing plate is an optical film formed by laminating a polarizing film and a phase difference plate, for example, in an organic EL image display device and other devices that display images in a planar state, it is used to prevent light reflection at the electrodes constituting the device. In recent years, there has been a continuous demand for lightweight and thin organic EL image display devices, and further thinning is also required for the phase difference plate and elliptically polarizing plate as one of its components. In such a case, the following types of optical films are known: after forming a functional layer such as a phase difference layer including a liquid crystal cured layer on a substrate film, the substrate film is peeled off, and the functional layer is transferred to other components such as a polarizing film and used as an optical film (patent document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-027431 Summary of the invention

[0006] Problems to be solved by the invention

[0007] From the perspective of improving productivity, it is advantageous to widen and / or lengthen the optical film having the transfer-type functional layer described above. When transferring the functional layer from the long optical film to another optical film, the so-called roll-to-roll method is generally used. However, for the functional layer including a liquid crystal cured layer formed by molecularly orienting and curing a polymerizable liquid crystal compound in a specific direction, when peeling off the base film during transfer, the following problem is likely to occur: the liquid crystal cured layer at the end in the short side direction is difficult to peel off linearly relative to the peeling direction (flow direction) of the base film, and the end of the liquid crystal cured layer is torn into a zigzag shape and detached.

[0008] Therefore, the object of the present invention is to provide a long strip film, which has a substrate film and a functional layer including a transferable liquid crystal cured layer, wherein the functional layer at the end in the short side direction is not easily detached when the substrate film is peeled off, and an optical film with excellent optical properties can be manufactured with good productivity.

[0009] Means for solving problems

[0010] The inventors of the present application have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. That is, the present invention includes the following aspects.

[0011] [1] A long film comprising:

[0012] A long strip-shaped substrate film having a concavo-convex portion at least at one end in the short side direction of at least one side; and

[0013] A transferable functional layer comprising a cured layer of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound,

[0014] The functional layer is laminated on the surface of the substrate film having the concavoconvex portion.

[0015] When the total width of the substrate film in the short side direction is A, the total width of the concave-convex portions of the substrate film in the short side direction is B, and the width of the functional layer in the short side direction is C, B+C>A is satisfied.

[0016] [2] The long film according to [1] above, wherein the peeling force of the functional layer from the base film is 0.02 N / 25 mm or more and less than 1 N / 25 mm.

[0017] [3] The long film according to [1] or [2] above, wherein the substrate film is a cellulose-based resin film or an olefin-based resin film.

[0018] [4] The long film as described in any one of [1] to [3] above, wherein the relationship between the average thickness X of the functional layer in the plane and the maximum height Y of the convex portion of the concavo-convex portion satisfies 1.0 <Y / X≤15.0。

[0019] [5] A long film as described in any one of [1] to [4] above, wherein the molecular orientation direction of the polymerizable liquid crystal compound in the above-mentioned cured layer constituting the functional layer is horizontal relative to the plane of the long side direction of the above-mentioned substrate film, and is not parallel to the long side direction of the above-mentioned substrate film.

[0020] [6] The long film according to any one of [1] to [5] above, wherein the cured layer constituting the functional layer satisfies the following formulas (1) and (2).

[0021] Re(450) / Re(550)≤1.00 (1)

[0022] 100nm≤Re(550)≤150nm (2)

[0023] [In formulas (1) and (2), Re(λ) represents the in-plane phase difference value at a wavelength of λ nm.]

[0024] [7] The long film according to any one of [1] to [5] above, wherein the cured layer constituting the functional layer satisfies the following formulas (3) and (4).

[0025] 200nm≤Re(550)≤300nm (3)

[0026] 1.00≤Re(450) / Re(550) (4)

[0027] [In formulas (3) and (4), Re(λ) represents the in-plane phase difference value at a wavelength of λ nm.]

[0028] [8] The long film according to any one of [1] to [7] above, wherein the functional layer includes a photo-alignment film.

[0029] [9] A long film as described in any one of [1] to [5] above, wherein the molecular orientation direction of the polymerizable liquid crystal compound in the above-mentioned cured layer constituting the functional layer is substantially vertical to the long side direction of the above-mentioned substrate film.

[0030]

[10] The long film according to any one of [1] to [5] and [9] above, wherein the cured layer constituting the functional layer satisfies the following formula (5).

[0031] -150nm≤Rth(550)≤-20nm (5)

[0032] [In formula (5), Rth(550) represents the phase difference value in the thickness direction of the cured layer at a wavelength of 550 nm.]

[0033] Effects of the Invention

[0034] According to the present invention, a long film having a substrate film and a functional layer including a transferable liquid crystal cured layer can be provided, wherein the functional layer is less likely to be detached at the ends in the short side direction when the substrate film is peeled off, and an optical film with excellent optical properties can be manufactured with good productivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] [ Figure 1 ] is a schematic cross-sectional view showing an example of the layer structure of the long film of the present invention as viewed from the short side direction. DETAILED DESCRIPTION

[0036] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.

[0037] The long film of the present invention comprises: a substrate film having a concavo-convex portion at at least one end portion in the short side direction of at least one side; and a transferable functional layer comprising a cured layer of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound. In the long film of the present invention, the transferable functional layer is laminated on one side of the substrate film having the concavo-convex portion, and when the total width in the short side direction of the substrate film is set to A, the total width in the short side direction of the concavo-convex portions present in the substrate film is set to B, and the width in the short side direction of the functional layer is set to C, B+C>A is satisfied.

[0038] Figure 1 This is a cross-sectional view showing an example of the layer structure of the long film of the present invention as viewed from the short side direction, but the present invention is not limited thereto. Figure 1 In the present invention, the long film 11 is formed by laminating a substrate film 1 and a functional layer 2. Concavoconvex portions 3 are provided at both ends of the substrate film 1 on the side laminated with the functional layer 2, and the functional layer 2 is laminated in a manner overlapping a portion of each concavoconvex portion 3. The total width in the short side direction of the substrate film 1 is set as A, and the sum of the widths in the short side direction of the concavoconvex portions 3 provided at both ends of the substrate film 1 is set as B ( Figure 1 (B1+B2 in the figure), when the total width of the functional layer 2 in the short side direction is set to C, B+C is greater than A.

[0039] In this specification, the so-called "transferable functional layer" refers to a layer that can be transferred to other substrates, optical films and other components after peeling off the substrate film, including a cured layer of a polymerizable liquid crystal compound containing a polymerizable liquid crystal compound (hereinafter, also referred to as a "liquid crystal cured layer"). As long as the functional layer does not affect the effect of the present invention and can function as an optical film after transfer, it can include layers other than the liquid crystal cured layer. As such other layers, there can be cited cured resin layers such as alignment films, protective layers, hard coatings, and adhesive layers for bonding functional layers such as liquid crystal cured layers to other components such as polarizing films. In the case where the long film of the present invention includes layers other than the substrate film and the liquid crystal cured layer, in this specification, all layers peeled off from the substrate film and transferred to other components are referred to as functional layers.

[0040] As mentioned above, the strip film of the present invention has the following structure: when the total width in the short side direction of the substrate film is set to A, the total width in the short side direction of the concavo-convex part present in the substrate film is set to B, and the width in the short side direction of the above-mentioned functional layer is set to C, B+C>A is satisfied. That is, in the strip film of the present invention, a portion of the functional layer is stacked on at least a portion of the concavo-convex part present in the substrate film. By providing the concavo-convex part at the end of the substrate film, when the functional layer is formed on the substrate film, an anchoring effect can be generated between the concavo-convex part and the functional layer stacked on the concavo-convex part, and the adhesion is easily improved. In addition, the adhesion of the area that is not in contact with the concavo-convex part is relatively reduced, so that when the functional layer is peeled off from the substrate film, the functional layer is easily peeled off along the concavo-convex part on the substrate film.

[0041] For example, by providing a concavoconvex portion in a straight line with a certain width along the long side direction at the end of the substrate film, the functional layer can be linearly peeled off relative to the peeling direction (flow direction) at the end of the long film. Thus, the detachment of the functional layer at the end of the long film during transfer can be suppressed, and the functional layer with a straight and neat end cross section can be transferred to other components, which can improve the operating efficiency and yield rate during use. In addition, at the concavoconvex portion covered by the functional layer, it is not easy to be squeezed during transportation or when stored in a roll, and it is not easy to deteriorate over time (Japanese: ヘタリ, the protrusion of the concavoconvex portion becomes smaller), so even after long-term storage, the functional layer can be easily and neatly peeled off from the substrate film.

[0042] The functional layer constituting the long film of the present invention is preferably laminated on the substrate film in the entire width direction of the functional layer. Therefore, the total width A in the short side direction of the substrate film and the width C in the short side direction of the functional layer are preferably in the relationship of A≥C, more preferably in the relationship of A>C.

[0043] In the present invention, it is preferred that the concavo-convex portion exists linearly at the end of the substrate film relative to the long side direction, and it is more preferred that the concavo-convex portion exists linearly at the two ends of the substrate film relative to the long side direction. In addition, it is more preferred that the two ends of the functional layer overlap and stack the concavo-convex portion existing at the two ends of the substrate film with a certain width. By making the long film have such a structure, the above-mentioned effect of the present invention can be further improved when the functional layer is peeled off from the substrate film and transferred to other parts. In addition, in order to improve the anchoring effect generated between the substrate film and the functional layer, the layer of the functional layer on one side adjacent to the substrate film is preferably a layer formed by curing after being directly coated on the substrate film, for example, preferably a liquid crystal cured material layer or a photo-alignment film.

[0044] In the present invention, the peel strength when peeling the functional layer from the base material film is preferably 0.02 N / 25 mm or more and less than 1 N / 25 mm. When the peel strength is within the above range, an appropriate adhesiveness is generated between the functional layer and the base material film, so that the functional layer can be peeled along the uneven portions of the base material film. At the same time, detachment caused by the attachment of the functional layer to a transfer roller or the like during transfer is suppressed, and since it has appropriate peelability, the functional layer can be easily and neatly peeled from the base material film. From the viewpoints of the peelability of the functional layer from the base material film and the appropriate adhesiveness, the above peel strength is more preferably 0.03 N / 25 mm or more, further preferably 0.05 N / 25 mm or more, and more preferably 0.5 N / 25 mm or less, further preferably 0.3 N / 25 mm or less. The peel strength can be controlled by the width of the uneven portions provided on the base material film, the height and / or shape of the unevenness, the material of the surface of the base material film or the functional layer in contact with the base material film, the conditions during coating and curing of the functional layer, and the like.

[0045] It should be noted that in the present invention, the above peel strength refers to the substrate peel strength (N / 25 mm) when peeling the substrate film at a speed of 300 mm / minute at the interface between the functional layer and the base material film or at the interface between the transferred layer in the functional layer and the layer peeled together with the base material film. Specifically, it can be measured according to the method described in the examples below.

[0046] In the present invention, the relationship between the in-plane average thickness X of the functional layer and the maximum height Y of the convex portion of the uneven portion preferably satisfies 1.0 < Y / X ≤ 15.0. By making the functional layer and the uneven portions on the base material film satisfy the above relationship, it is easy to improve the operability of the long strip film, and in addition, it is also easy to improve the following effects: suppressing winding deviation when the long strip film is wound into a roll and deformation (adhesion) during long-term storage. If the value of Y / X is too large, it is easy to cause obvious adhesion at the film end, and there are also likely to be more deformations in the in-plane film roll. In the present invention, the value of Y / X is more preferably 1.5 or more, further preferably 2.0 or more, and more preferably 12.0 or less, further preferably 10.0 or less.

[0047] In the present invention, the "in-plane average thickness of the functional layer" refers to the in-plane average value obtained by measuring the total thickness of all layers constituting the functional layer in the short side direction within the range not including the portion overlapping with the uneven portions of the base material film. In addition, the "maximum height of the convex portion of the uneven portion" refers to the height from the surface of the base material film without uneven portions to the vertex of the convex portion having the maximum height in the uneven portion. Regarding the in-plane average thickness X of the functional layer and the maximum height Y of the convex portion of the uneven portion, each can be measured using, for example, a contact type film thickness gauge. Specifically, it can be measured according to the method described in the examples below.

[0048] As the substrate film constituting the long film of the present invention, for example, thin film glass, resin film, etc. can be cited. From the viewpoint of processability, resin film is preferred. As the resin constituting the resin film, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers can be cited; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; plastics such as polyphenylene sulfide and polyphenylene ether. Such resins can be made into substrates by known means such as solvent casting and melt extrusion. The surface of the substrate film can be subjected to surface treatments such as demolding treatment, corona treatment, plasma treatment, etc., such as silicone treatment, as long as the effect of the present invention is not affected.

[0049] As the substrate film, commercially available products can be used. As commercially available cellulose ester substrates, for example, cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd. such as Fujitack Film can be cited. As commercially available cyclic olefin resins, for example, cyclic olefin resins manufactured by Ticona (Germany) such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation such as "ARTON (registered trademark)"; cyclic olefin resins manufactured by Zeon Co., Ltd. such as "ZEONOR (Zeonor) (registered trademark)" and "ZEONEX (Zeonex) (registered trademark)"; cyclic olefin resins manufactured by Mitsui Chemicals, Inc. such as "Apel (registered trademark)". Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin-based resin substrates include cyclic olefin-based resin substrates manufactured by Sekisui Chemical Co., Ltd., such as “Escena (registered trademark)” and “SCA40 (registered trademark)”; cyclic olefin-based resin substrates manufactured by OPTES Corporation, such as “ZEONORFILM (registered trademark)”; and cyclic olefin-based resin substrates manufactured by JSR Corporation, such as “ARTONFILM (registered trademark)”.

[0050] From the viewpoints of thinness, ease of peeling of the functional layer from the substrate film, ease of orientation of the polymerizable liquid crystal compound, solvent resistance and low birefringence, as the substrate film, a cellulose resin film or an olefin resin film is preferred, and a cellulose resin film is more preferred. Generally, for a cellulose resin film manufactured by a solvent casting method, it is difficult to impart slippage to the film surface, and the adhesion with the layer stacked on the film becomes high, and when it is wound into a long strip roll, it is easy to adhere. In addition, when the long film roll is unwound, the following situation may occur: due to the close fit of the functional layer and the substrate film on the back, peeling occurs randomly and part of it falls off. In such a case, by providing a concavo-convex portion at the end of the substrate, the adhesion between the concavo-convex portion and the functional layer is further improved, and a gap is provided between the functional layer and the substrate film on the back in the region without concavo-convex, thereby suppressing the adhesion and peeling in the region without concavo-convex, so that a moderate difference is generated in the adhesion between the substrate film and the functional layer between the concavo-convex portion and the region without concavo-convex, thereby making it easy to peel the functional layer straightly from the substrate film along the peeling direction. Therefore, the present invention is particularly advantageous when a cellulose resin film is used.

[0051] In the present invention, the concavo-convex part on the substrate film is called the so-called roller pattern, and generally functions as a structure for suppressing contact and adhesion between substrate surfaces when the substrate film is rolled up. The shape, material, and formation method of such concavo-convex part can be appropriately selected from the conventionally known shapes, materials, and formation methods according to the substrate film constituting the long film, the functional layer, the desired peeling force, etc.

[0052] The concavoconvex portion is preferably formed in a desired region at the end of the substrate film when the substrate film is wound, for example. The concavoconvex portion may be formed on only one side of the substrate film, or may be formed on both sides. In addition, the concavoconvex portion may be provided only at at least one end of the substrate film, but is preferably provided at both ends of the substrate film in order to obtain good peelability of the functional layer from the substrate film.

[0053] The concavoconvex part is preferably arranged in a strip shape parallel to the long side direction at the end of the short side direction of the substrate film. The short side width of the concavoconvex part arranged in a strip shape can be appropriately determined according to the short side width of the long film, the substrate film constituting the long film, the functional layer, the desired peeling force, the thickness of the long film, etc. Usually, at each end, each is about 0.2 to 5% of the short side width of the substrate film. If the short side width of each concavoconvex part is within the above range, it is easy to produce a moderate anchoring effect between the concavoconvex part and the functional layer, and it is easy to obtain good peelability between the substrate film and the functional layer. For example, in the case of a substrate film with a short side width of 1000 to 2000 mm, the short side width of the concavoconvex part is preferably 1 mm or more, more preferably 3 mm or more, and more preferably 5 mm or more. In addition, it is preferably 50 mm or less, more preferably 30 mm or less, and more preferably 20 mm or less.

[0054] The height of the concavoconvex part can be appropriately determined according to the width in the short side direction of the long film, the width in the short side direction of the concavoconvex part, the thickness of the functional layer, the substrate film constituting the long film, the functional layer, the desired peeling force, the thickness of the long film, etc. It is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 200 μm or less, and further preferably 20 μm or less. If the height of each concavoconvex part is within the above range, it is easy to produce a moderate anchoring effect between the concavoconvex part and the functional layer, and it is easy to obtain good peelability between the substrate film and the functional layer.

[0055] It should be noted that the height of the so-called concavoconvex part here refers to the average height of each concavoconvex part when the surface of the substrate film without the concavoconvex part in the substrate film without the laminated functional layer is used as the reference. Specifically, for example, a contact film thickness meter can be used to measure the range of the substrate film without the concavoconvex part at a spacing of 1 mm along the width direction, thereby calculating the average total thickness. Similarly, the range of the concavoconvex part at the end of the same position in the width direction is measured to calculate the average total thickness of the concavoconvex part, thereby measuring and calculating the average height of the concavoconvex part based on the difference.

[0056] Concave and convex parts per 1cm 2 The number (density) of the concavoconvex is preferably 20 or more, more preferably 50 or more, and preferably 1000 or less, more preferably 500 or less, and further preferably 200 or less. It is preferred that the concavoconvex portions are uniformly present.

[0057] When the density of each concavo-convex portion is within the above range, a moderate anchor effect is likely to occur between the concavo-convex portion and the functional layer, and good releasability between the base film and the functional layer is likely to be obtained.

[0058] As the shape of each concavoconvex part constituting the concavoconvex part, for example, a pyramidal trapezoid, a conical trapezoid, a dome shape, a corrugated shape, a lattice shape, an amorphous shape, etc. can be cited. The size of each concavoconvex part can be appropriately determined according to the width in the short side direction of the long film, the width in the short side direction of the concavoconvex part, the density of the concavoconvex part, the base film constituting the long film, the functional layer, the desired peeling force, the thickness of the long film, etc. For example, when the cross-sectional shape of the concavoconvex part when the base film surface and the film surface are cut parallel to each other is circular or substantially circular, the diameter of the cross-sectional shape is preferably about 50 to 1000 μm, and more preferably 100 to 3000 μm.

[0059] As a method for forming a concavo-convex portion on a substrate film, for example, a method of clamping with a pair of rollers is usually used. It can be a single-sided pressing using an embossed roller only on one side of a pair of rollers, or it can be a double-sided pressing using an embossed roller on both sides. In addition, lasers etc. can also be used for processing. As a specific example of such a concavo-convex portion, for example, the concavo-convex portions recorded in International Publication No. 2010 / 143524, Japanese Patent Publication No. 2007-91784, etc. can be cited.

[0060] As the substrate film having uneven portions, commercially available products may be used. Examples of commercially available products include cellulose ester substrates such as "KC8UX2M", "KC8UY", and "KC4UY" manufactured by Konica Minolta Opto, Inc.

[0061] The thickness of the substrate film may be appropriately determined depending on the material of the substrate film, and is usually 5 to 300 μm, preferably 10 to 150 μm, and more preferably 20 to 80 μm from the viewpoint of elongation of the film and quality after winding.

[0062] The width of the substrate film in the short side direction is preferably 0.5 to 3 m, more preferably 0.6 to 2.5 m, and even more preferably 0.8 to 2.2 m. The long film is preferably wound into a roll, and its length is preferably 100 to 10,000 m per roll, more preferably 500 to 7,000 m, and even more preferably 1,000 to 6,000 m.

[0063] The functional layer constituting the long film of the present invention comprises a cured layer of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound. The cured layer is a liquid crystal cured layer formed by curing the polymerizable liquid crystal compound in a state of being oriented in a specific direction such as a horizontal direction or a vertical direction relative to the plane of the cured layer.

[0064] In the present invention, the polymerizable liquid crystal compound is a liquid crystal compound having a polymerizable group, especially a photopolymerizable group. As the polymerizable liquid crystal compound, there is no particular limitation as long as it can form a liquid crystal cured material layer having desired optical properties, for example, a polymerizable liquid crystal compound previously known in the field of phase difference film can be used.

[0065] A polymerizable group refers to a group that can participate in a polymerization reaction. The so-called photopolymerizable group refers to a polymerizable group that can participate in a polymerization reaction through reactive species such as active free radicals, acids, etc. generated by a photopolymerization initiator. As a photopolymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetane are preferred, and acryloyloxy is more preferred. Regarding the liquid crystal properties displayed by the polymerizable liquid crystal compound, it can be a thermotropic liquid crystal or a lyotropic liquid crystal, but from the perspective of being able to perform precise film thickness control, it is preferably a thermotropic liquid crystal. In addition, as a phase-ordered structure in a thermotropic liquid crystal, it can be a nematic liquid crystal, a smectic liquid crystal, or a discotic liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.

[0066] As the polymerizable liquid crystal compound, there can be mentioned a polymerizable liquid crystal compound that generally exhibits positive wavelength dispersion and a polymerizable liquid crystal compound that exhibits reverse wavelength dispersion, and only any one of the polymerizable liquid crystal compounds can be used, or two polymerizable liquid crystal compounds can be mixed and used. From the perspective of easily improving the front reflection hue and easily obtaining a long film with excellent optical properties in an image display device that is assembled with a functional layer by transfer from the long film of the present invention, it is preferred to include the following polymerizable liquid crystal compound, that is, a polymer obtained by polymerizing a polymerizable liquid crystal compound in a state where it is oriented alone in a specific direction and exhibiting reverse wavelength dispersion.

[0067] From the perspective of easily exhibiting reverse wavelength dispersion, a polymerizable liquid crystal compound having a so-called T-shaped or H-shaped molecular structure is preferred, and from the perspective of obtaining stronger reverse wavelength dispersion, a polymerizable liquid crystal compound having a T-shaped molecular structure is more preferred.

[0068] As the polymerizable liquid crystal compound, a compound having the following characteristics (A) to (D) is preferred.

[0069] (A) is a compound that can form a nematic phase or a smectic phase.

[0070] (B) The polymerizable liquid crystal compound has π electrons in the long-axis direction (a).

[0071] (C) It has π electrons in a direction intersecting the long axis direction (a) (intersecting direction (b)).

[0072] (D) The π electron density in the long axis direction (a) of the polymerizable liquid crystal compound is defined by the following formula (i), where the total number of π electrons present in the long axis direction (a) is N(πa) and the total molecular weight present in the long axis direction is N(Aa):

[0073] D(πa)=N(πa) / N(Aa) (i), and,

[0074] The total number of π electrons present in the cross direction (b) is denoted as N(πb), and the total number of molecular weights present in the cross direction (b) is denoted as N(Ab), and the π electron density in the cross direction (b) of the polymerizable liquid crystal compound is defined by the following formula (ii):

[0075] D(πb)=N(πb) / N(Ab) (ii)

[0076] The relationship of existence (iii) is:

[0077] 0≤〔D(πa) / D(πb)〕<1 (iii)

[0078] [That is, the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a)].

[0079] As described above, a polymerizable liquid crystal compound having π electrons in the long axis and in a direction intersecting therewith usually tends to have a T-shaped structure.

[0080] In the above-mentioned features (A) to (D), the major axis direction (a) and the number of π electrons N are defined as follows.

[0081] The major axis direction (a) refers to the major axis direction of the rod, for example, in the case of a compound having a rod-like structure.

[0082] The number of π electrons N(πa) present in the major axis direction (a) does not include π electrons that disappear due to the polymerization reaction.

[0083] The number of π electrons N(πa) present in the long axis direction (a) is the total number of π electrons on the long axis and π electrons conjugated thereto, for example, including the number of π electrons present in the ring that exists in the long axis direction (a) and satisfies the Huckel rule.

[0084] The number of π electrons N(πb) present in the crossing direction (b) does not include π electrons that disappear due to the polymerization reaction.

[0085] The polymerizable liquid crystal compound satisfying the above conditions has a mesostructure in the long axis direction. The mesostructure exhibits a liquid crystal phase (nematic phase, smectic phase). In one embodiment of the present invention, the polymerizable liquid crystal compound is preferably a compound capable of forming a nematic phase.

[0086] By applying a polymerizable liquid crystal compound satisfying the above (A) to (D) on a film (layer) forming a liquid crystal cured film and heating it to a phase transition temperature or above, a nematic phase or a smectic phase can be formed. The nematic phase or smectic phase formed by the orientation of the polymerizable liquid crystal compound is usually oriented in a manner that the long axis directions of the polymerizable liquid crystal compound are parallel to each other, and the long axis direction becomes the orientation direction of the nematic phase or the smectic phase. If such a polymerizable liquid crystal compound is made into a film and polymerized in a nematic phase or a smectic phase, a polymer film formed by polymerizing in a state oriented along the long axis direction (a) can be formed. The polymer film absorbs ultraviolet rays by π electrons in the long axis direction (a) and π electrons in the cross direction (b). Here, the absorption maximum wavelength of ultraviolet rays absorbed by π electrons in the cross direction (b) is recorded as λbmax. λbmax is usually 300nm to 400nm. The density of π electrons satisfies the above formula (iii), and the density of π electrons in the cross direction (b) is greater than that in the long axis direction (a), so that the absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the cross direction (b) is greater than that of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the long axis direction (a). The ratio (absorbance in the cross direction (b) of linearly polarized ultraviolet light / absorbance in the long axis direction (a)) is, for example, greater than 1.0, preferably greater than 1.2, and usually 30 or less, for example, 10 or less.

[0087] Generally, when polymerizable liquid crystal compounds having the above characteristics are polymerized in a state of being oriented in one direction, the birefringence of the polymer often shows reverse wavelength dispersion. Specifically, for example, there can be mentioned compounds represented by the following formula (X).

[0088]

[0089] In formula (X), Ar represents a divalent group having an aromatic group which may have a substituent. Here, the so-called aromatic group includes, for example, the groups exemplified by (Ar-1) to (Ar-23) described later. In addition, Ar may have two or more aromatic groups. The aromatic group may contain at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the number of aromatic groups contained in Ar is two or more, the two or more aromatic groups may be bonded to each other by divalent bonding groups such as a single bond, -CO-O-, or -O-.

[0090] G 1 and G 2Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.

[0091] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.

[0092] k and l each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.

[0093] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. In addition, the hydrogen atoms contained in the alkanediyl group may be substituted with halogen atoms, and the -CH 2 - may be replaced by -O-, -S-, or -C(=O)-.

[0094] P 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0095] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms. More preferably, it is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group. Especially preferably, it is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.

[0096] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0097] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、-R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH 2 -、-CH 2 CH 2 -、-COOR a4-1 -, or -OCOR a6-1 -. Here, R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH 2 -、-CH 2 CH 2 -Any one of L 1 and L 2 Each of them is independently more preferably a single bond, -O-, -CH 2 CH 2 -、-COO-、-COOCH 2 CH 2 -, or -OCO-.

[0098] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-Ra13 OCOR a14 -, or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH 2 -、-CH 2 CH 2 -、-COOR a12 -1 -, or -OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH 2 -、-CH 2 CH 2 -Any one of B. 1 and B 2 Each of them is independently more preferably a single bond, -O-, -CH 2 CH 2 -、-COO-、-COOCH 2 CH 2 -, -OCO-, or -OCOCH 2 CH 2 -.

[0099] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, k+l=4 is preferred, and k=2 and l=2 are more preferred. k=2 and l=2 are preferred because a symmetrical structure is obtained.

[0100] As P 1 or P 2 Examples of the polymerizable group represented by include epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxiranyl, and oxetanyl.

[0101] Among them, an acryloyloxy group, a methacryloyloxy group, a vinyl group, and a vinyloxy group are preferred, and an acryloyloxy group and a methacryloyloxy group are more preferred.

[0102] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, benzene ring, naphthalene ring, anthracene ring, etc. can be cited, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring, etc. can be cited. Among them, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazole ring. In addition, when Ar contains nitrogen atom, the nitrogen atom preferably has π electrons.

[0103] In formula (X), the total number of π electrons possessed by the group represented by Ar is N π It is usually 6 or more, preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 32 or less, more preferably 26 or less, and further preferably 24 or less.

[0104] Examples of the aromatic group contained in Ar include the following groups.

[0105]

[0106] In the formulas (Ar-1) to (Ar-23), the symbol * represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 A polymerizable group may be contained.

[0107] Q 1 and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or -O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0108] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.

[0109] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.

[0110] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.

[0111] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, which contain at least one hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom, preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.

[0112] Y 1 , Y 2 and Y 3 Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.

[0113] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferably, Z is a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 A polymerizable group may be contained.

[0114] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 2’-、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.

[0115] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0116] In the formulas (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic rings that Ar may have and are described above, for example, a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, a pyrrolidine ring, etc. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z that can be bonded to it 0 Together, they form the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.

[0117] In the present invention, as a polymerizable liquid crystal compound forming a liquid crystal cured material layer, for example, a compound containing a group represented by the following formula (Y) (hereinafter also referred to as "polymerizable liquid crystal compound (Y)") can be used. The polymerizable liquid crystal compound (Y) generally tends to show positive wavelength dispersion. These polymerizable liquid crystal compounds can be used alone or in combination of two or more.

[0118] P11-B11-E11-B12-A11-B13-(Y)

[0119] [In formula (Y), P11 represents a polymerizable group.

[0120] A11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group.

[0121] B11 represents -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -、-NR 16 -CO-, -CO-, -CS- or a single bond. 16 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.

[0122] B12 and B13 each independently represent -C≡C-, -CH=CH-, -CH 2 -CH 2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -、-NR 16 -C(=O)-, -OCH 2 -、-OCF 2 -、-CH 2 O-、-CF 2 O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH-, -H, -C≡N or a single bond.

[0123] E11 represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group may be substituted by an alkoxy group having 1 to 5 carbon atoms, and the hydrogen atoms contained in the alkoxy group may be substituted by a halogen atom. 2 - may be replaced by -O- or -CO-.]

[0124] The number of carbon atoms in the aromatic hydrocarbon group and alicyclic hydrocarbon group represented by A11 is preferably in the range of 3 to 18, more preferably in the range of 5 to 12, and particularly preferably 5 or 6. The hydrogen atoms contained in the divalent alicyclic hydrocarbon group and divalent aromatic hydrocarbon group represented by A11 may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group or a nitro group, and the hydrogen atoms contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom. As A11, cyclohexane-1,4-diyl and 1,4-phenylene are preferred.

[0125] E11 is preferably a linear alkanediyl group having 1 to 12 carbon atoms. 2 - can be replaced by -O-.

[0126] Specifically, there can be mentioned a straight-chain alkanediyl group having 1 to 12 carbon atoms, such as methylene, ethylene, propane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, nonane-1,9-diyl, decane-1,10-diyl, undecane-1,11-diyl and dodecane-1,12-diyl; -CH 2 -CH 2 -O-CH 2 -CH 2 -、-CH 2 -CH 2 -O-CH 2 -CH 2 -O-CH 2 -CH 2- and - CH 2 -CH 2 -O-CH 2 -CH 2 -O-CH 2 -CH 2 -O-CH 2 -CH 2 -wait.

[0127] B11 is preferably -O-, -S-, -CO-O-, and -O-CO-, and among them, -CO-O- is more preferred.

[0128] As B12 and B13, each independently, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, and -OC(=O)-O- are preferred, and among them, -O- or -OC(=O)-O- is more preferred.

[0129] As the polymerizable group represented by P11, from the perspective of high polymerization reactivity, especially photopolymerization reactivity, it is preferably a free radical polymerizable group or a cationic polymerizable group. From the perspective of easy operation and easy manufacture of the liquid crystal compound itself, the polymerizable group is preferably a group represented by the following formula (P-11) to (P-15).

[0130]

[0131] [In formulas (P-11) to (P-15),

[0132] R 17 ~R 21 Each independently represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom.]

[0133] Specific examples of the groups represented by formula (P-11) to formula (P-15) include groups represented by the following formula (P-16) to formula (P-20).

[0134]

[0135] P11 is preferably a group represented by formula (P-14) to formula (P-20), and more preferably a vinyl group, a p-stilbene group, an epoxy group, or an oxetanyl group.

[0136] The group represented by P11-B11- is more preferably an acryloyloxy group or a methacryloyloxy group.

[0137] Examples of the polymerizable liquid crystal compound (Y) include compounds represented by formula (I), formula (II), formula (III), formula (IV), formula (V) or formula (VI).

[0138] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12(I)

[0139] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11(II)

[0140] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12(III)

[0141] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11(IV)

[0142] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12(V)

[0143] P11-B11-E11-B12-A11-B13-A12-F11(VI)

[0144] [Wherein,

[0145] A11, B11~B13 and P11 have the same meanings as above.

[0146] A12 to A14 each independently have the same meaning as A11, B14 to B16 each independently have the same meaning as B12, B17 has the same meaning as B11, E12 has the same meaning as E11, and P12 has the same meaning as P11.

[0147] F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfone group (-SO 3 H), a carboxyl group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, the -CH 2 - can be replaced by -O-. ]

[0148] Specific examples of polymerizable liquid crystal compounds (Y) include compounds having polymerizable groups recorded in "3.8.6 Network (Completely Cross-linked Type)" and "6.5.1 Liquid Crystal Materials b. Polymerizable Nematic Liquid Crystal Materials" of Liquid Crystal Handbook (edited by Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2000), and polymerizable liquid crystals recorded in Japanese Patent Publication No. 2010-31223, Japanese Patent Publication No. 2010-270108, Japanese Patent Publication No. 2011-6360 and Japanese Patent Publication No. 2011-207765.

[0149] As specific examples of polymerizable liquid crystal compounds (Y), compounds represented by the following formulas (I-1) to (I-4), (II-1) to (II-4), (III-1) to (III-26), (IV-1) to (IV-26), (V-1) to (V-2) and (VI-1) to (VI-6) can be cited. It should be noted that in the following formula, k1 and k2 each independently represent an integer of 2 to 12. These polymerizable liquid crystal compounds (Y) are preferred from the perspective of ease of synthesis or ease of acquisition.

[0150]

[0151]

[0152]

[0153]

[0154]

[0155]

[0156]

[0157] The polymerizable liquid crystal compounds (X) and (Y) may be used after being aligned horizontally or vertically.

[0158] Among the polymerizable liquid crystal compounds, polymerizable liquid crystal compounds having a maximum absorption wavelength between 300 and 400 nm are preferred. When a photopolymerization initiator is included in the polymerizable liquid crystal composition, it is possible to carry out polymerization reaction and gelation of the polymerizable liquid crystal compound during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300 to 400 nm, even if it is exposed to ultraviolet light during storage, it is possible to effectively suppress the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species. Therefore, it is advantageous from the perspective of the long-term stability of the polymerizable liquid crystal composition, and the orientation and uniformity of the film thickness of the obtained liquid crystal cured film can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and chloroform and the like can be cited as examples.

[0159] Relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition, the content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. When the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal cured layer. It should be noted that when the polymerizable liquid crystal composition includes two or more polymerizable liquid crystal compounds, the total amount of all liquid crystal compounds contained in the polymerizable liquid crystal composition is preferably within the range of the above content. In addition, in this specification, the solid content of the polymerizable liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymerizable liquid crystal composition.

[0160] The polymerizable liquid crystal composition may contain, in addition to the polymerizable liquid crystal compound, additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, a photosensitizer, a vertical alignment promoter, and a polymerizable non-liquid crystal compound. Each of these components may be used alone or in combination of two or more.

[0161] The polymerizable liquid crystal composition is usually applied to a substrate film or the like in a state dissolved in a solvent, and therefore preferably contains a solvent. As the solvent, a solvent that can dissolve the polymerizable liquid crystal compound is preferred, and a solvent that is inactive in the polymerization reaction of the polymerizable liquid crystal compound is preferred. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone; and the like. These solvents can be used alone or in combination of two or more. Among them, from the viewpoint of film coating, it is preferred to use at least one selected from alcohol solvents, ester solvents, ketone solvents, chlorinated solvents, amide solvents and aromatic hydrocarbon solvents, and from the viewpoint of the solubility of polymerizable liquid crystal compounds, it is more preferred to use at least one selected from ester solvents, ketone solvents, amide solvents and aromatic hydrocarbon solvents.

[0162] Relative to 100 parts by mass of polymerizable liquid crystal composition, the content of the solvent in the polymerizable liquid crystal composition is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by weight. Therefore, the solid component preferably accounts for 2 to 50 parts by mass in 100 parts by mass of the polymerizable liquid crystal composition. When the solid component is less than 50 parts by mass, the viscosity of the polymerizable liquid crystal composition decreases, so the thickness of the film becomes roughly uniform, and there is a tendency to be less prone to unevenness. The above-mentioned solid component can be appropriately determined considering the thickness of the polymerizable liquid crystal cured material layer to be manufactured.

[0163] The polymerization initiator is a compound that generates reactive species by the contribution of heat or light and can initiate a polymerization reaction of a polymerizable liquid crystal compound or the like. As reactive species, there can be mentioned active species such as free radicals, cations or anions. Among them, from the viewpoint of easy control of the reaction, a photopolymerization initiator that generates free radicals by light irradiation is preferred.

[0164] Examples of the photopolymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, oxime compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts. Specific examples thereof include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, and Irgacure 379EG (all manufactured by BASF Japan Co., Ltd.), SEIKUOL BZ, SEIKUOL Z, and SEIKUOL BEE (all manufactured by Seiko Chemical Industries, Ltd.), kayacure BP100 (manufactured by Nippon Kayaku Co., Ltd.), kayacure UVI-6992 (manufactured by DOW), ADEKA OPTOMER SP-152, and ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARKLS NCI-831, ADEKA ARKLS NCI-930 (all manufactured by ADEKA Corporation), TAZ-A, TAZ-PP (all manufactured by Nippon Siber Hegner Co., Ltd.), and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0165] The photopolymerization initiator contained in the polymerizable liquid crystal composition is at least one kind, and may be used in combination of two or more kinds, but is preferably one kind or two kinds.

[0166] The photopolymerization initiator preferably has a maximum absorption wavelength of 300 nm to 400 nm, more preferably 300 nm to 380 nm, in order to fully utilize the energy emitted from the light source and achieve excellent productivity. Among them, α-acetophenone-based polymerization initiators and oxime-based photopolymerization initiators are preferred.

[0167] Examples of the α-acetophenone compound include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)-1-butanone. More preferred examples include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone. Examples of commercially available α-acetophenone compounds include Irgacure 369, 379EG, and 907 (all manufactured by BASF Japan Co., Ltd.) and SEIKUOL BEE (manufactured by Seiko Chemical Co., Ltd.).

[0168] Oxime ester photopolymerization initiators generate free radicals such as phenyl radicals and methyl radicals by irradiating light. The polymerization of polymerizable liquid crystal compounds is appropriately carried out by the free radicals, wherein the oxime ester photopolymerization initiators that can generate methyl radicals are preferred from the perspective of the high initiation efficiency of the polymerization reaction. In addition, from the perspective of making the polymerization reaction more efficiently carried out, it is preferred to use a photopolymerization initiator that can efficiently utilize ultraviolet rays of more than 350nm in wavelength. As a photopolymerization initiator that can efficiently utilize ultraviolet rays of more than 350nm in wavelength, it is preferably a triazine compound or a carbazole compound containing an oxime ester structure, and from the perspective of sensitivity, it is more preferably a carbazole compound containing an oxime ester structure. Examples of the carbazole compound containing an oxime ester structure include 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], O-acetyl-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(acetone oxime), etc. Examples of commercially available products of oxime ester-based photopolymerization initiators include Irgacure OXE-01, Irgacure OXE-02, and Irgacure OXE-03 (all manufactured by BASF Japan Co., Ltd.), ADEKA OPTOMER N-1919, and ADEKA ARKLS NCI-831 (all manufactured by ADEKA Co., Ltd.).

[0169] The content of the photopolymerization initiator is usually 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. Within the above range, the reaction of the polymerizable group proceeds sufficiently and the alignment of the polymerizable liquid crystal compound is less likely to be disturbed.

[0170] In the present invention, an antioxidant may be added to the composition for the purpose of controlling the stability of the composition. The antioxidant may be a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants.

[0171] When the polymerizable group of the polymerizable liquid crystal compound is a radical polymerizable group, phosphorus-based antioxidants and sulfur-based antioxidants are preferred as secondary antioxidants from the viewpoint of being less likely to inhibit the reaction.

[0172] The content of the antioxidant is preferably 0.01 to 3.0 parts by mass, more preferably 0.01 to 1.0 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0173] By using a sensitizer, the photopolymerization initiator can be highly sensitive. Examples of photosensitizers include xanthones such as xanthone and thioxanthone; anthracenes and anthracenes having a substituent such as an alkyl ether; phenothiazine; and rubrene. Examples of photosensitizers include xanthones such as xanthone and thioxanthone; anthracenes and anthracenes having a substituent such as an alkyl ether; phenothiazine; and rubrene.

[0174] The content of the photosensitizer is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0175] The leveling agent is an additive having the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the coating film obtained by applying the composition flatter, and examples thereof include silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents.As the leveling agent, commercially available products can be used, and specific examples thereof include DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, and FZ2123 (all manufactured by Dow Corning Toray Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, and KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, and TSF4460 (all manufactured by Momentive Performance Materials Japan LLC), fluorinert (registered trademark) FC-72, fluorinert FC-40, fluorinert FC-43, fluorinert FC-3283 (all manufactured by Sumitomo 3M Co., Ltd.), MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAFACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-477, MEGAFACE F-479, MEGAFACE F-482, MEGAFACE F-483 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF303, EFTOP EF351, EFTOP EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all of which are manufactured by AGC Seimi Chemical Co., Ltd.), trade name E1830, trade name E5844 (manufactured by Daikin Fine Chemical Kenkyusho, KK), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade names: manufactured by BM Chemie), etc. The leveling agent can be used alone or in combination of two or more.

[0176] The content of the leveling agent is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the resulting liquid crystal cured layer tends to be smoother, which is preferred.

[0177] The polymerizable liquid crystal composition can be obtained by stirring a polymerizable liquid crystal compound and components other than the polymerizable liquid crystal compound, such as a solvent and a photopolymerization initiator, at a predetermined temperature.

[0178] In one embodiment of the present invention, the cured product layer (liquid crystal cured product layer) included in the functional layer has the optical properties represented by the following formulas (1) and (2). The liquid crystal cured product layer is usually a cured product formed by curing a polymerizable liquid crystal compound in a state of being oriented in a horizontal direction relative to the plane of the cured product layer (hereinafter also referred to as a "horizontally oriented liquid crystal cured product layer").

[0179] Re(450) / Re(550)≤1.00 (1)

[0180] 100nm≤Re(550)≤150nm (2)

[0181] [In formulas (1) and (2), Re(λ) represents the in-plane phase difference value at a wavelength of λ nm.]

[0182] When formula (1) is satisfied, the liquid crystal cured material layer exhibits a so-called reverse wavelength dispersion in which the in-plane phase difference at a short wavelength is smaller than the in-plane phase difference at a long wavelength. In order to improve the reverse wavelength dispersion and improve the front hue of the elliptically polarizing plate obtained by transferring the functional layer including the liquid crystal cured material layer from the long film of the present invention to the polarizing film when applied to a display device, Re (450) / Re (550) is preferably 0.70 or more, more preferably 0.78 or more, and preferably less than 1, more preferably 0.95 or less, and further preferably 0.92 or less.

[0183] The above-mentioned in-plane phase difference value can be adjusted by the thickness dA of the liquid crystal cured layer. The in-plane phase difference value is determined by the following formula, so in order to obtain the desired in-plane phase difference value (Re (λ): the in-plane phase difference value of the liquid crystal cured layer at wavelength λ (nm)), it is sufficient to adjust the three-dimensional refractive index and the layer thickness dA.

[0184] Re(λ)=(nxA(λ)-nyA(λ))×dA

[0185] [wherein, nxA(λ) represents the principal refractive index at wavelength λ in the plane of the liquid crystal cured material layer, nyA(λ) represents the refractive index at wavelength λ in the direction orthogonal to the direction of nxA in the same plane as nxA, and dA represents the layer thickness of the liquid crystal cured material layer]

[0186] It should be noted that the three-dimensional refractive index depends on the molecular structure and orientation state of the polymerizable liquid crystal compound.

[0187] In addition, if the in-plane phase difference Re(550) of the liquid crystal cured material layer is within the range of formula (2), the liquid crystal cured material layer functions as a so-called λ / 4 plate, and the front reflection color tone is improved when the functional layer containing it is applied to a display device. A further preferred range of the in-plane phase difference value is 130nm≤Re(550)≤150nm.

[0188] The cured product layer included in the functional layer may have the optical properties represented by the following formula (3) instead of the above formula (2). In this case, it preferably has the optical properties satisfying the formula (4).

[0189] Such a liquid crystal cured material layer is also generally a horizontally aligned liquid crystal cured material layer in which the polymerizable liquid crystal compound is cured in a state of being aligned in a horizontal direction with respect to the plane of the cured material layer.

[0190] 200nm≤Re(550)≤300nm (3)

[0191] 1.00≤Re(450) / Re(550) (4)

[0192] [In formulas (3) and (4), Re(λ) represents the in-plane phase difference value of the liquid crystal cured layer at a wavelength of λ nm.]

[0193] If the liquid crystal cured material layer satisfies formulas (3) and (4), the liquid crystal cured material layer functions as a so-called λ / 2 plate, and the front reflection hue is improved when the functional layer containing the liquid crystal cured material layer is applied to a display device. The further preferred range of the in-plane phase difference value Re(550) at this time is 220nm≤Re(550)≤280nm.

[0194] In another embodiment of the present invention, the cured product layer (liquid crystal cured product layer) contained in the functional layer has the optical properties represented by the following formula (5). The liquid crystal cured product layer is usually a cured product formed by curing a polymerizable liquid crystal compound in a state of being oriented in a vertical direction relative to the plane of the liquid crystal cured product layer (hereinafter also referred to as a "vertically oriented liquid crystal cured product layer").

[0195] -150nm≤Rth(550)≤-20nm (5)

[0196] [In formula (5), Rth(550) represents the phase difference value in the thickness direction of the cured layer at a wavelength of 550 nm.]

[0197] If the phase difference value Rth(550) in the thickness direction of the liquid crystal cured material layer is within the range of formula (5), the effect of improving the oblique reflection color tone when the functional layer containing it is applied to a display device is excellent. A further preferred range of the phase difference value is -30nm≤Rth(550)≤-100nm.

[0198] In the present invention, when the cured layer included in the functional layer is a vertically aligned liquid crystal cured layer, the liquid crystal cured layer preferably satisfies the following formula (6), and more preferably satisfies both formula (5) and formula (6).

[0199] Rth(450) / Rth(550)≤1.00 (6)

[0200] [In formula (6), Rth(λ) represents the phase difference value in the thickness direction of the cured layer at a wavelength of λ nm.]

[0201] By satisfying the above formula (5), the decrease in ellipticity at the short wavelength side in the functional layer including the vertically aligned liquid crystal cured layer can be suppressed, and the oblique reflection hue can be improved. The value of the above Rth(450) / Rth(550) is more preferably less than 0.95, more preferably less than 0.92, and particularly preferably less than 0.9. In addition, it is preferably more than 0.7, more preferably more than 0.75, and more preferably more than 0.8. It should be noted that Rth(λ) can be controlled by the three-dimensional refractive index and the film thickness dC.

[0202] The above-mentioned phase difference value in the thickness direction is determined by the following formula: Rth(λ)=((nxC(λ)+nyC(λ)) / 2-nzC(λ))×dC. Therefore, in order to obtain the desired phase difference value Rth(550) in the film thickness direction, it is sufficient to adjust the three-dimensional refractive index and film thickness dC.

[0203] [wherein nxC(λ) represents the in-plane principal refractive index of the liquid crystal cured material layer at a wavelength of λ nm, nyC(λ) represents the refractive index in a direction orthogonal to nxC(λ) in the plane at a wavelength of λ nm, nzC(λ) represents the refractive index in the thickness direction of the liquid crystal cured material layer at a wavelength of λ nm, when nxC(λ)=nyC(λ), nxC(λ) can be the refractive index in any direction in the film plane, and dC represents the film thickness of the liquid crystal cured material layer]

[0204] It should be noted that the three-dimensional refractive index depends on the molecular structure and alignment state of the polymerizable liquid crystal compound.

[0205] The thickness of the liquid crystal solidified material layer is preferably 0.1 to 5.0 μm, more preferably 0.2 to 4.0 μm, and further preferably 0.4 to 3.0 μm. When the thickness of the liquid crystal solidified material layer increases, the mechanical strength is also improved, and there is a tendency that the functional layer is not easy to break. If the thickness of the liquid crystal solidified material layer is within the above range, the functional layer is easily torn when it is transferred to other optical films, etc. In the present invention, since a part of the functional layer is laminated on the concave-convex portion provided at the end of the substrate film, the occurrence of tearing can be effectively suppressed by the moderate anchoring effect generated at the end. In the case of a thickness within the above range, it is easy to obtain the effect of the present invention more significantly.

[0206] The long film of the present invention can be produced, for example, by a method comprising the following steps:

[0207] A step of forming a coating film of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound on a long substrate film or an alignment film described later, drying the coating film, and orienting the polymerizable liquid crystal compound in the polymerizable liquid crystal composition; and,

[0208] A step of polymerizing the polymerizable liquid crystal compound by irradiating light while maintaining the aligned state to form a liquid crystal cured material layer.

[0209] In the present invention, the coating film of the polymerizable liquid crystal composition can be formed by coating the polymerizable liquid crystal composition on the substrate film constituting the long film of the present invention, or on the oriented film formed on the long substrate film as described later. As a method for coating the polymerizable liquid crystal composition on the substrate film, etc., known methods such as spin coating, extrusion, gravure coating, die coating, rod coating, coating method such as applicator method, printing method such as offset method can be cited.

[0210] Next, the solvent is removed by drying, etc. to form a dry coating. As a drying method, natural drying, ventilation drying, heating drying and reduced pressure drying methods, etc. can be cited. At this time, by heating the coating obtained by the polymerizable liquid crystal composition, the polymerizable liquid crystal compound can be oriented in a desired direction (for example, horizontal or vertical direction) relative to the coating plane while the solvent is dried and removed from the coating. The heating temperature of the coating can be appropriately determined by considering the materials of the polymerizable liquid crystal compound used and the substrate to be formed, but in order to make the polymerizable liquid crystal compound phase change to a liquid crystal phase state, usually, it is necessary to be a temperature above the liquid crystal phase transition temperature. In order to remove the solvent contained in the polymerizable liquid crystal composition and make the polymerizable liquid crystal compound become the desired orientation state, for example, it can be heated to a temperature above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the above-mentioned polymerizable liquid crystal composition.

[0211] The heating temperature is preferably 3° C. or higher than the liquid crystal phase (nematic phase) transition temperature of the polymerizable liquid crystal compound, and more preferably 5° C. or higher. The upper limit of the heating temperature is not particularly limited, but is preferably 180° C. or lower, and more preferably 150° C. or lower, in order to avoid damage to the coating film, substrate, etc. caused by heating.

[0212] It should be noted that the liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc., which are equipped with a temperature regulating station. In addition, when two or more kinds are used in combination as polymerizable liquid crystal compounds, the above-mentioned phase transition temperature refers to: a mixture of polymerizable liquid crystal compounds obtained by mixing all polymerizable liquid crystal compounds constituting a polymerizable liquid crystal composition in the same ratio as the composition in the polymerizable liquid crystal composition, and the temperature measured by operating in the same manner as when using one polymerizable liquid crystal compound. In addition, it is known that the following situation is usually present: the liquid crystal phase transition temperature of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is lower than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound monomer.

[0213] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc., and is usually 0.5 to 10 minutes, preferably 0.5 to 5 minutes.

[0214] The removal of the solvent from the coating can be carried out simultaneously with the heating of the polymerizable liquid crystal compound to the liquid crystal phase transition temperature or above, or it can be carried out independently, but from the viewpoint of improving productivity, it is preferably carried out simultaneously. Before the heating of the polymerizable liquid crystal compound to the liquid crystal phase transition temperature or above is carried out, a pre-drying process for appropriately removing the solvent in the coating under the condition that the polymerizable liquid crystal compound contained in the coating obtained by the polymerizable liquid crystal composition is not polymerized can be provided. As the drying method in the pre-drying process, natural drying method, ventilation drying method, heating drying and reduced pressure drying method, etc. can be cited, and the drying temperature (heating temperature) in the drying process can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc.

[0215] Next, in the obtained dry coating, while maintaining the orientation state of the polymerizable liquid crystal compound, the polymerizable liquid crystal compound is polymerized by light irradiation, thereby forming a polymer of the polymerizable liquid crystal compound existing in the desired orientation state, i.e., a vertically oriented liquid crystal cured film. As a polymerization method, thermal polymerization and photopolymerization can be cited, but from the viewpoint of easy control of polymerization reaction, photopolymerization is preferred. In photopolymerization, as the light irradiated to the dry coating, it can be appropriately selected according to the type of photopolymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount. As a specific example thereof, one or more light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, active energy rays such as active electron rays can be cited. Among them, from the aspect of easily controlling the progress of the polymerization reaction, the aspect that a device widely used in the art can be used as a photopolymerization device, preferably ultraviolet light, preferably in a manner that ultraviolet light can be used for photopolymerization, the type of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition is preselected. In addition, during polymerization, by irradiating light while cooling the dried coating using appropriate cooling means, the polymerization temperature can also be controlled. If the polymerization of the polymerizable liquid crystal compound is implemented at a lower temperature by adopting such a cooling means, even if the substrate uses a substance with lower heat resistance, a liquid crystal solidification layer can be appropriately formed. In addition, within the range of the undesirable conditions caused by the heat during light irradiation (deformation of the substrate due to heat, etc.), the polymerization reaction can also be promoted by increasing the polymerization temperature. During photopolymerization, by shielding, developing, etc., a patterned solidified layer can also be obtained.

[0216] As the light source of the aforementioned active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.

[0217] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and further preferably 0.1 second to 1 minute. When irradiation is performed once or more times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm2 .

[0218] When the accumulated light amount is within this range, the polymerizable liquid crystal composition is sufficiently cured, and good transferability can be obtained. In addition, coloring of the entire long film including the liquid crystal cured material layer can be suppressed.

[0219] In one embodiment of the present invention, a liquid crystal solidified material layer may be formed on an alignment film. The alignment film has an alignment control force that allows the polymerizable liquid crystal compound to be oriented in the desired direction. Among them, an alignment film having an alignment control force that allows the polymerizable liquid crystal compound to be oriented in the horizontal direction is sometimes referred to as a horizontal alignment film, and an alignment film having an alignment control force that allows the polymerizable liquid crystal compound to be oriented in the vertical direction is sometimes referred to as a vertical alignment film. By forming a liquid crystal solidified material layer on the alignment film, a liquid crystal solidified material layer in which the polymerizable liquid crystal compound is oriented with good precision can be obtained, and a functional layer that exhibits excellent optical properties when assembled to a display device can be obtained. The alignment control force can be arbitrarily adjusted by the type of alignment film, the surface state, the friction conditions, etc., and when the alignment film is formed by a photo-aligned polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.

[0220] As an alignment film, it is preferred to have solvent resistance that does not dissolve due to the coating of a polymerizable liquid crystal composition, and heat resistance in a heating treatment for removing a solvent and orienting a polymerizable liquid crystal compound. As an alignment film, an alignment film comprising an oriented polymer, a photoalignment film, a groove alignment film having a concave-convex pattern and a plurality of grooves on the surface, a stretched film stretched along the orientation direction, etc. are cited. From the perspective of the accuracy and quality of the orientation angle, a photoalignment film is preferred.

[0221] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and polyamic acids as their hydrolyzates, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.

[0222] An oriented film containing an oriented polymer can be generally obtained by applying a composition obtained by dissolving an oriented polymer in a solvent (hereinafter, also referred to as an "oriented polymer composition") to a surface such as a substrate film on which the oriented film is to be formed, and removing the solvent; or, applying the oriented polymer composition to a substrate, removing the solvent, and rubbing (rubbing method). As the solvent, the same solvent as the solvent exemplified above as a solvent that can be used in a polymerizable liquid crystal composition can be cited.

[0223] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably about 0.1 to 20%, more preferably about 0.1 to 10%, in terms of solid content relative to the solution.

[0224] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTOMER (registered trademark, manufactured by JSR Corporation).

[0225] Examples of a method for applying the oriented polymer composition to a surface such as a substrate film on which an oriented film is to be formed include the same methods as those exemplified as the method for applying the polymerizable liquid crystal composition to the substrate.

[0226] Examples of a method for removing the solvent contained in the oriented polymer composition include a natural drying method, a ventilation drying method, a heat drying method, and a reduced pressure drying method.

[0227] In order to impart an orientation control force to the oriented film, a rubbing treatment (rubbing method) may be performed as required. As a method of imparting an orientation control force by rubbing, there can be cited a method of bringing an oriented polymer film formed on the surface of a substrate by coating an oriented polymer composition on a substrate and annealing the oriented polymer composition into contact with a rubbing roller wound with a rubbing cloth and rotating. When performing the rubbing treatment, if shielding is performed, multiple regions (patterns) with different orientation directions can also be formed in the oriented film.

[0228] The photo-alignment film can be generally obtained by applying a composition containing a polymer and / or a monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") to the surface of the substrate on which the alignment film is to be formed, removing the solvent, and irradiating the substrate with polarized light (preferably polarized UV light). The photo-alignment film can be advantageously obtained by arbitrarily controlling the direction of the alignment control force by selecting the polarization direction of the irradiated polarized light.

[0229] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, which become the source of liquid crystal orientation ability, can be cited. Among them, the group participating in the dimerization reaction or the photocrosslinking reaction is preferred from the aspect of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).

[0230] Examples of the photoreactive group having a C═C bond include a vinyl group, a polyene group, a stilbene group, a stilbazole group, a stilbazolium group, a chalcone group, and a cinnamoyl group.

[0231] As photoreactive groups having a C=N bond, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having an N=N bond, groups such as azophenyl, azonaphthyl, aromatic heterocyclic azo, disazo, formazan, and groups having an oxyazobenzene structure can be cited. As photoreactive groups having a C=O bond, groups such as benzophenone, coumarin, anthraquinone, and maleimide can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.

[0232] Among them, photoreactive groups that participate in the photodimerization reaction are preferred. From the perspective that the amount of polarized light irradiation required for photo-alignment is small and a photo-alignment film with excellent thermal stability and temporal stability is easily obtained, the photoreactive groups are preferably cinnamoyl and chalcone groups. In particular, when the liquid crystal cured layer is formed of a polymerizable liquid crystal compound having a (meth)acryloyloxy group as a polymerizable group, in order to further improve the adhesion with the liquid crystal cured layer, as a polymer having a photoreactive group that forms the alignment film, a polymer having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred.

[0233] Examples of the solvent contained in the photo-alignment film-forming composition include the same solvents as those exemplified above as the solvents that can be used in the polymerizable liquid crystal composition, and the solvent can be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.

[0234] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of polymer or monomer and the thickness of the target photo-alignment film, and is preferably set to at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. In addition, with respect to the polymer forming the photo-alignment film, from the aspect of easy manufacture and the aspect of being able to improve the adhesion with the liquid crystal cured layer when the oriented liquid crystal cured layer is formed by a polymerizable liquid crystal compound having a (meth) acryloyloxy group as a polymerizable group, it is preferably a (meth) acrylic polymer. Within the range that does not significantly affect the properties of the photo-alignment film, the composition for forming a photo-alignment film may include polymer materials such as polyvinyl alcohol and polyimide, and a photosensitizer.

[0235] As a method for applying the composition for forming a photo-alignment film on the surface where the alignment film is to be formed, the same method as the method for applying the alignment polymer composition can be cited. As a method for removing the solvent from the applied composition for forming a photo-alignment film, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.

[0236] When irradiating polarized light, the product obtained by removing the solvent from the composition for forming a photo-alignment film applied on the surface (the surface where the alignment film is to be formed) can be directly irradiated with polarized UV light. In addition, it is particularly preferred that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400 nm is particularly preferred. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among them, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because of the large luminous intensity of ultraviolet rays with a wavelength of 313 nm. Polarized UV light can be irradiated by passing light from the aforementioned light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.

[0237] In addition, when rubbing or polarized light irradiation is performed, if shielding is performed, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.

[0238] The groove oriented film is a film having a concave-convex pattern or multiple grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules are oriented in the direction along the grooves.

[0239] As methods for obtaining a grooved orientation film, the following methods can be cited: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then performing development and rinsing treatment to form a concave-convex pattern; a method of forming a layer of a UV-curable resin before curing on a plate-like original plate having grooves on its surface, transferring the formed resin layer to a surface such as a substrate film on which an orientation film is to be formed, and then curing it; and a method of pushing a rolled original plate having a plurality of grooves against a film of a UV-curable resin before curing formed on the surface on which an orientation film is to be formed to form concave-convex patterns, and then curing it; and the like.

[0240] The thickness of the alignment film (alignment film or photoalignment film containing an aligning polymer) is usually in the range of 10 to 10000 nm, preferably 10 to 2500 nm, more preferably 10 to 1000 nm or less, further preferably 10 to 500 nm, particularly preferably 50 to 250 nm.

[0241] In the present invention, when the liquid crystal curing material layer constituting the functional layer is a vertically oriented liquid crystal curing material layer, the liquid crystal curing material layer is made to include at least one vertical orientation promoter, so that the liquid crystal curing material layer can be directly formed on the surface of the substrate film where the liquid crystal curing material layer is to be formed without the above-mentioned orientation film. In this specification, the so-called vertical orientation promoter refers to a material that promotes the liquid crystal orientation of the polymerizable liquid crystal compound in a vertical direction relative to the plane of the curing material layer. By making the liquid crystal curing material layer include a vertical orientation promoter, a vertically oriented liquid crystal curing material layer can be directly formed without forming a vertically oriented film on the substrate film, so that the manufacturing process of the long film is simplified, and the long film can be manufactured with good productivity.

[0242] As a vertical orientation promoter, it is preferred that when a polymerizable liquid crystal composition is applied to a substrate film, a component that generates electrostatic repulsion to the polymerizable liquid crystal compound at the substrate film side interface of the coating film. As such a component, for example, an ionic compound can be cited. From the viewpoint of suppressing the generation of orientation defects of the liquid crystal cured layer, as a vertical orientation promoter, it is preferred to include an ionic compound formed by non-metallic atoms. When the polymerizable liquid crystal composition containing a polymerizable liquid crystal compound includes an ionic compound formed by non-metallic atoms, in the dried coating formed by the composition, electrostatic interactions are usually performed to show a vertical orientation control force for the polymerizable liquid crystal compound, and the polymerizable liquid crystal compound can be oriented in a vertical direction relative to the film plane in the dried coating. Thus, a liquid crystal cured layer can be formed while maintaining the vertical orientation of the polymerizable liquid crystal compound.

[0243] As the ionic compound formed by non-metallic atoms (hereinafter, also referred to as "ionic compound"), for example, onium salts (more specifically, quaternary ammonium salts, tertiary sulfonium salts, and quaternary phosphonium salts in which the nitrogen atom has a positive charge, etc.) can be cited. Among these onium salts, quaternary onium salts are preferred from the viewpoint of further improving the vertical alignment of the polymerizable liquid crystal compound, and quaternary phosphonium salts or quaternary ammonium salts are more preferred from the viewpoint of improving the availability and mass production.

[0244] The onium salt may have two or more quaternary onium salt sites in the molecule, and may be an oligomer or a polymer.

[0245] The molecular weight of the ionic compound is preferably 100 to 10,000. When the molecular weight is within the above range, it is easy to improve the vertical alignment of the polymerizable liquid crystal compound while ensuring the coating property of the polymerizable liquid crystal composition. The molecular weight of the ionic compound is more preferably 5000 or less, and further preferably 3000 or less.

[0246] As the cationic component of the ionic compound, for example, inorganic cations and organic cations can be cited. Among them, organic cations are preferred from the perspective of not being easy to produce orientation defects of polymerizable liquid crystal compounds. As organic cations, for example, imidazolium cations, pyridinium cations, ammonium cations, sulfonium cations and phosphonium cations can be cited.

[0247] Ionic compounds usually have counter anions. As anionic components that become counter ions of the above-mentioned cationic components, for example, inorganic anions and organic anions can be cited. Among them, from the aspect of not being easy to produce the orientation defects of polymerizable liquid crystal compounds, organic anions are preferred. It should be noted that cations and anions do not necessarily correspond one to one.

[0248] Specific examples of the anion component include the following anions.

[0249] Chloride anion - 〕、

[0250] Bromide anion - 〕、

[0251] Iodide anion - 〕、

[0252] Tetrachloroaluminate anion 〔AlCl 4 - 〕、

[0253] Heptachlorodialuminate anion 2 Cl 7 - 〕、

[0254] Tetrafluoroborate anion 〔BF 4 - 〕、

[0255] Hexafluorophosphate anion 6 - 〕、

[0256] Perchlorate anion 〔ClO 4 - 〕、

[0257] Nitrate anion 〔NO 3 - 〕、

[0258] Acetate anion 〔CH 3 COO - 〕、

[0259] Trifluoroacetate anion [CF 3 COO - 〕、

[0260] Fluorosulfonate anion 〔FSO 3 - 〕、

[0261] Methanesulfonate anion 〔CH 3 SO 3 - 〕、

[0262] trifluoromethanesulfonate anion 〔CF 3 SO 3 - 〕、

[0263] p-Toluenesulfonate anion 3 C 6 H 4 SO 3 - 〕、

[0264] Bis(fluorosulfonyl)imide anion〔(FSO 2 ) 2 N - 〕、

[0265] Bis(trifluoromethanesulfonyl)imide anion〔(CF 3 SO 2 ) 2 N - 〕、

[0266] tris(trifluoromethanesulfonyl)methane anion〔(CF 3 SO 2 ) 3 C - 〕、

[0267] Hexafluoroarsenate anion 6 - 〕、

[0268] Hexafluoroantimonate anion 〔SbF 6 - 〕、

[0269] Hexafluoroniobate anion〔NbF 6 - 〕、

[0270] Hexafluorotantalate anion 〔TaF 6 - 〕、

[0271] Dimethylphosphinate anion〔(CH 3 ) 2 POO - 〕、

[0272] (poly)hydrofluorofluoride anion〔F(HF) n - 〕(for example, n represents an integer from 1 to 3),

[0273] Dicyanamide anion〔(CN) 2 N - 〕、

[0274] SCN - 〕、

[0275] Perfluorobutanesulfonate anion 4 F 9 SO 3 - 〕、

[0276] Bis(pentafluoroethanesulfonyl)imide anion 2 F 5 SO 2 ) 2 N - 〕、

[0277] Perfluorobutyrate anion 3 F 7 COO - 〕,and

[0278] (Trifluoromethanesulfonyl)(trifluoromethanecarbonyl)imide anion

[0279] 〔(CF 3 SO 2 )(CF 3 CO)N- 〕.

[0280] Specific examples of the ionic compound can be appropriately selected from the above-mentioned combinations of cationic components and anionic components. Specific examples of the compound of the combination of a cationic component and anionic component include the following compounds.

[0281] (Pyridinium salt)

[0282] N-hexylpyridinium hexafluorophosphate,

[0283] N-octylpyridinium hexafluorophosphate,

[0284] N-methyl-4-hexylpyridinium hexafluorophosphate,

[0285] N-butyl-4-methylpyridinium hexafluorophosphate,

[0286] N-octyl-4-methylpyridinium hexafluorophosphate,

[0287] Bis(fluorosulfonyl)imide N-hexylpyridinium,

[0288] Bis(fluorosulfonyl)imide N-octylpyridinium,

[0289] N-methyl-4-hexylpyridinium bis(fluorosulfonyl)imide,

[0290] N-butyl-4-methylpyridinium bis(fluorosulfonyl)imide,

[0291] Bis(fluorosulfonyl)imide N-octyl-4-methylpyridinium,

[0292] N-hexylpyridinium bis(trifluoromethanesulfonyl)imide,

[0293] N-octylpyridinium bis(trifluoromethanesulfonyl)imide,

[0294] N-methyl-4-hexylpyridinium bis(trifluoromethanesulfonyl)imide,

[0295] N-butyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide,

[0296] Bis(trifluoromethanesulfonyl)imide N-octyl-4-methylpyridinium,

[0297] N-hexylpyridinium p-toluenesulfonate,

[0298] N-Octylpyridinium p-toluenesulfonate,

[0299] N-methyl-4-hexylpyridinium p-toluenesulfonate,

[0300] N-butyl-4-methylpyridinium p-toluenesulfonate, and

[0301] N-Octyl-4-methylpyridinium p-toluenesulfonate.

[0302] (Imidazolium salt)

[0303] 1-Ethyl-3-methylimidazolium hexafluorophosphate,

[0304] 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide,

[0305] 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide,

[0306] 1-Ethyl-3-methylimidazolium p-toluenesulfonate,

[0307] 1-Butyl-3-methylimidazolium methanesulfonate, etc.

[0308] (Pyrrolidinium salt)

[0309] N-butyl-N-methylpyrrolidinium hexafluorophosphate,

[0310] Bis(fluorosulfonyl)imide N-butyl-N-methylpyrrolidinium,

[0311] N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide,

[0312] N-butyl-N-methylpyrrolidinium p-toluenesulfonate, etc.

[0313] (Ammonium salt)

[0314] Tetrabutylammonium hexafluorophosphate,

[0315] Tetrabutylammonium bis(fluorosulfonyl)imide,

[0316] Tetrahexyl ammonium bis(fluorosulfonyl)imide,

[0317] Bis(fluorosulfonyl)imide trioctylmethylammonium,

[0318] Bis(fluorosulfonyl)imide (2-hydroxyethyl)trimethylammonium,

[0319] Tetrabutylammonium bis(trifluoromethanesulfonyl)imide,

[0320] Tetrahexylammonium bis(trifluoromethanesulfonyl)imide,

[0321] Bis(trifluoromethanesulfonyl)imide trioctylmethylammonium,

[0322] Bis(trifluoromethanesulfonyl)imide (2-hydroxyethyl)trimethylammonium,

[0323] Tetrabutylammonium p-toluenesulfonate,

[0324] Tetrahexyl ammonium p-toluenesulfonate,

[0325] Trioctylmethylammonium p-toluenesulfonate,

[0326] (2-Hydroxyethyl)trimethylammonium p-toluenesulfonate,

[0327] (2-Hydroxyethyl)trimethylammonium dimethylphosphinate,

[0328] Bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylpropyl)-1,1,1-tributylammonium,

[0329] 1-(3-trimethoxysilylpropyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide,

[0330] Bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylbutyl)-1,1,1-tributylammonium,

[0331] 1-(3-trimethoxysilylbutyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide,

[0332] Bis(trifluoromethanesulfonyl)imide N-{(3-triethoxysilylpropyl)carbamoyloxyethyl)}-N,N,N-trimethylammonium, and

[0333] Bis(trifluoromethanesulfonyl)imide N-[2-{3-(3-trimethoxysilylpropylamino)-1-oxopropoxy}ethyl]-N,N,N-trimethylammonium.

[0334] (Phosphonium salt)

[0335] Bis(trifluoromethanesulfonyl)imide tributyl(2-methoxyethyl)phosphonium,

[0336] Bis(trifluoromethanesulfonyl)imide tributylmethylphosphonium,

[0337] 1,1,1-trimethyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide,

[0338] 1,1,1-trimethyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide,

[0339] 1,1,1-trimethyl-1-[3-(trimethoxysilyl)propyl]phosphonium bis(trifluoromethanesulfonyl)imide,

[0340] 1,1,1-trimethyl-1-[4-(trimethoxysilyl)butyl]phosphonium bis(trifluoromethanesulfonyl)imide,

[0341] 1,1,1-tributyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide,

[0342] 1,1,1-tributyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide, and

[0343] 1,1,1-tributyl-1-[3-(trimethoxysilyl)propyl]phosphonium bis(trifluoromethanesulfonyl)imide.

[0344] These ionic compounds may be used alone or in combination of two or more. Among them, ionic compounds composed of phosphonium salts, pyridinium salts, and ammonium salts are preferred.

[0345] From the viewpoint of being able to further improve the vertical alignment of the polymerizable liquid crystal compound, the ionic compound preferably has Si element and / or F element in the molecular structure of the cationic part. When the ionic compound has Si element and / or F element in the molecular structure of the cationic part, it is easy to segregate the ionic compound on the surface of the cured layer formed by the polymerizable liquid crystal compound. Among them, as an ionic compound whose constituent elements are all non-metallic elements, the following ionic compounds (i) to (iii) are preferred.

[0346] (Ionic compound (i))

[0347]

[0348] (Ionic compound (ii))

[0349]

[0350] (Ionic compound (iii))

[0351]

[0352] For example, a method of improving the orientation of liquid crystal by treating the surface of the substrate with a surfactant having a long alkyl group of a certain chain length (for example, see Chapter 2 of "Liquid Crystal Handbook: Orientation and Physical Properties of Liquid Crystals" (published by Maruzen Co., Ltd.) etc.) can be applied to further improve the vertical orientation of the polymerizable liquid crystal compound. That is, by treating the surface of the substrate with an ionic compound having a long alkyl group of a certain chain length, the vertical orientation of the polymerizable liquid crystal compound can be effectively improved.

[0353] Specifically, the ionic compound preferably satisfies the following formula (7).

[0354] 5 <M<16 (7)

[0355] In formula (7), M is represented by the following formula (8).

[0356] M = (the number of covalent bonds from the positively charged atom to the molecular chain terminal of the substituent with the largest number of covalent bonds to the molecular chain terminal among the substituents directly bonded to the positively charged atom) ÷ (the number of positively charged atoms) (8)

[0357] When the ionic compound satisfies the above-mentioned (7), the vertical alignment property of the polymerizable liquid crystal compound can be effectively improved.

[0358] It should be noted that, when there are two or more atoms with positive charge in the molecule of the ionic compound, for a substituent having two or more atoms with positive charge, the number of covalent bonds from the atom with positive charge regarded as the base point to the closest other atom with positive charge is taken as the "number of covalent bonds from the atom with positive charge to the end of the molecular chain" described in the above definition of M. In addition, when the ionic compound is an oligomer or polymer having two or more repeating units, the constituent unit is regarded as one molecule and the above M is calculated. When the atom with positive charge is incorporated in a ring structure, the number of covalent bonds from the atom with positive charge via the ring structure or the number of covalent bonds to the end of the substituent bonded to the ring structure, whichever has more covalent bonds, is taken as the "number of covalent bonds from the atom with positive charge to the end of the molecular chain" described in the above definition of M.

[0359] With regard to the content of the ionic compound formed by the non-metallic atoms in the polymerizable liquid crystal composition, generally, relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition, it is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, further preferably 0.1 parts by mass or more, in addition, preferably 5 parts by mass or less, more preferably 4 parts by mass or less, further preferably 3 parts by mass or less. If the content of the ionic compound formed by the non-metallic atoms is within the above range, it is possible to effectively promote the vertical orientation of the polymerizable liquid crystal compound while maintaining the good coating property of the polymerizable liquid crystal composition.

[0360] As a vertical orientation promoter, the following components may be included: when a polymerizable liquid crystal composition is applied to a substrate film, the surface energy of the interface of the obtained solidified material layer on the opposite side to the substrate film can be reduced, thereby exerting a vertical orientation control force that makes the polymerizable liquid crystal compound oriented in a vertical direction relative to the film plane. As such a component, for example, nonionic silane compounds, leveling agents, etc. can be cited, preferably nonionic silane compounds. When the polymerizable liquid crystal composition contains a nonionic silane compound, the nonionic silane compound reduces the surface tension of the composition, and in the dry coating formed by the composition, there is a tendency that the nonionic silane compound is biased at the interface between the dry coating and the air, and the vertical orientation control force for the polymerizable liquid crystal compound can be increased, and the polymerizable liquid crystal compound is oriented in a vertical direction relative to the film plane in the dry coating. Thus, a liquid crystal cured material layer can be formed while maintaining the vertical orientation of the polymerizable liquid crystal compound.

[0361] Nonionic silane compounds are nonionic compounds containing Si elements. As nonionic silane compounds, for example, silicone polymers such as polysilane, silicone resins such as silicone oil and silicone resins, and organo-inorganic silane compounds (more specifically, silane coupling agents, etc.) such as silicone oligomers, silsesquioxanes and alkoxysilanes can be cited. These nonionic silane compounds can be used alone or in combination of two or more. Among them, from the viewpoint of further improving the adhesion with adjacent layers, preferably silane coupling agents.

[0362] The nonionic silane compound may be a silicone monomer type or a silicone oligomer (polymer) type. When the silicone oligomer is represented in the form of a (monomer)-(monomer) copolymer, examples include: copolymers containing a mercaptopropyl group such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, and 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; and copolymers containing a mercaptopropyl group such as mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, and mercaptomethyltriethoxysilane-tetraethoxysilane copolymer. 3-methacryloxypropyl trimethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl trimethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl triethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl triethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl methyl dimethoxysilane-tetramethoxysilane copolymer, 3-methacryloxypropyl methyl dimethoxysilane-tetraethoxysilane copolymer, 3-methacryloxypropyl methyl diethoxysilane-tetramethoxysilane copolymer and 3-methacryloxypropyl methyl Copolymers containing methacryloxypropyl groups such as diethoxysilane-tetraethoxysilane copolymers; 3-acryloxypropyl trimethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl trimethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl triethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl triethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl methyldimethoxysilane-tetramethoxysilane copolymers, 3-acryloxypropyl methyldimethoxysilane-tetraethoxysilane copolymers, 3-acryloxypropyl methyldiethoxysilane-tetramethoxysilane copolymers and Copolymers containing an acryloxypropyl group such as 3-acryloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer; copolymers containing a vinyl group such as vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, and vinylmethyldiethoxysilane-tetraethoxysilane copolymer;Copolymers containing amino groups such as 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer and 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer. ;

[0363] Silane coupling agent is a compound having at least one functional group selected from the group consisting of vinyl, epoxy, styryl, methacryloyl, acryl, amino, isocyanurate, urea, sulfydryl, isocyanate, carboxyl, and hydroxyl at the end, and at least one alkoxysilyl or silanol group, containing Si element. By appropriately selecting these functional groups, it is possible to give excellent effects such as the improvement of the mechanical strength of the vertically oriented liquid crystal curing material layer, surface modification, and the improvement of the adhesion of the layer adjacent to the liquid crystal curing material layer. From the viewpoint of adhesion, silane coupling agent is preferably a silane coupling agent with an alkoxysilyl and another different reactive group (for example, the above-mentioned functional group). Silane coupling agent is further preferably a silane coupling agent with an alkoxysilyl and a polar group. When silane coupling agent has at least one alkoxysilyl and at least one polar group in its molecule, the vertical orientation of polymerizable liquid crystal compound is easily further improved, and there is a trend that can significantly obtain a vertical orientation promotion effect. Examples of the polar group include an epoxy group, an amino group, an isocyanurate group, a mercapto group, a carboxyl group, and a hydroxyl group. In addition, the polar group may have a substituent or a protecting group as appropriate in order to control the reactivity of the silane coupling agent.

[0364] Specific examples of the silane coupling agent include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-glycidoxypropyltrimethoxysilane, 3-Glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane and 3-glycidoxypropylethoxydimethylsilane.

[0365] Examples of commercially available silane coupling agents include KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, and KBM-503. 3. Silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., such as KBE-502, KBE-503, KBM-5103, KBM-602, KBM-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBM-9659, KBE-585, KBM-802, KBM-803, KBE-846, and KBE-9007.

[0366] The content of the nonionic silane compound in the polymerizable liquid crystal composition is generally preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more, relative to 100 parts by mass of the polymerizable liquid crystal compound contained in the composition. In addition, it is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and further preferably 3 parts by mass or less.

[0367] When the content of the nonionic silane compound is within the above range, the vertical alignment of the polymerizable liquid crystal compound can be effectively promoted while maintaining good coating properties of the polymerizable liquid crystal composition.

[0368] In the present invention, the polymerizable liquid crystal composition for forming a vertically oriented liquid crystal cured layer preferably includes at least one of an ionic compound and a nonionic silane compound formed by non-metallic atoms as a vertical orientation promoter, more preferably includes an ionic compound formed by non-metallic atoms, and more preferably includes both an ionic compound and a nonionic silane compound formed by non-metallic atoms. The polymerizable liquid crystal composition comprises both an ionic compound and a nonionic silane compound formed by non-metallic atoms, so that in the dried coating formed by the polymerizable liquid crystal composition, the electrostatic interaction of the ionic compound formed by non-metallic atoms at the interface on the substrate side and the surface energy reduction effect of the non-ionic silane compound at the interface on the non-substrate side are generated at the two interfaces of the liquid crystal cured layer. The vertical orientation control force of the polymerizable liquid crystal compound is generated, and therefore, it is easy to further promote the vertical orientation of the polymerizable liquid crystal compound. Thus, it is possible to form a liquid crystal cured layer while maintaining the polymerizable liquid crystal compound in a state of further accurately oriented vertically.

[0369] Furthermore, by adding a polymerizable non-liquid crystal compound (hereinafter also referred to as a "pre-reaction compound") such as a compound having a functional group reactive with a hydroxyl group or a carboxyl group and a (meth) acryloyl group in the molecule to the polymerizable liquid crystal composition for forming a vertically aligned liquid crystal cured product layer, the adhesion with the substrate having hydroxyl groups or carboxyl groups on the surface by corona treatment, plasma treatment, etc. can be improved, and by adjusting the surface treatment state of the substrate, the type and content of the pre-reaction compound contained in the vertically aligned liquid crystal cured film, etc., the substrate peeling force P of the laminate can be controlled. Thus, a long film can be obtained in which the vertically aligned liquid crystal cured product layer formed without a vertically aligned film is laminated with the substrate film with the best adhesion and exhibits the best substrate peeling force.

[0370] In the present invention, when the molecular orientation direction of the polymerizable liquid crystal compound in the liquid crystal cured product constituting the functional layer is horizontal relative to the long side direction of the substrate film and is not parallel to the long side direction of the substrate film, its effect is easy to become significant. The so-called molecular orientation direction of the polymerizable liquid crystal compound is not parallel to the long side direction of the substrate film, which means that the polymerizable liquid crystal compound is horizontally oriented, and its orientation direction is not parallel to the long side direction. When the long side direction of the substrate film is in the above-mentioned relationship with the orientation direction of the polymerizable liquid crystal compound, it is possible to use a roll-to-roll method to transfer the functional layer from the long strip film of the present invention and attach the long strip to the optical film of the polarizing film having an absorption axis or a transmission axis in the long side direction described later. On the other hand, since the molecular orientation direction of the polymerizable liquid crystal compound is not consistent with the peeling direction, that is, the long side direction during transfer, the end of the liquid crystal cured material layer is easily torn into a serrated shape. In such a case, by providing a concave-convex portion at the end of the substrate, the adhesion between the concave-convex portion and the functional layer is further improved, and in the area without concave-convex, a fine gap is provided between the functional layer and the substrate film on the back side, thereby suppressing adhesion and detachment in the area without concave-convex, so that a moderate difference is generated in the adhesion between the substrate film and the functional layer between the concave-convex portion and the area without concave-convex, thereby making it easy to peel the functional layer from the substrate film in a straight line along the peeling direction, suppressing the occurrence of tearing at the end during transfer, and ensuring high productivity and quality.

[0371] In addition, when the molecular orientation direction of the polymerizable liquid crystal compound in the liquid crystal cured material constituting the functional layer is substantially vertical relative to the long side direction of the substrate film, the effect is also likely to become significant. The so-called molecular orientation direction of the polymerizable liquid crystal compound is vertical relative to the long side direction of the substrate film, which means that the polymerizable liquid crystal compound is vertically oriented. In such a case, similar to the case where the polymerizable liquid crystal compound is horizontally oriented in the liquid crystal cured material layer, since the molecular orientation direction of the polymerizable liquid crystal compound is not consistent with the peeling direction, that is, the long side direction during transfer, the end of the liquid crystal cured material layer is easily torn into a serrated shape. However, by providing a concave-convex portion at the end of the substrate, a moderate difference is generated in the adhesion between the concave-convex portion and the area without concave-convex portions, thereby making it easy to peel the functional layer from the substrate film in a straight line along the peeling direction, suppressing the occurrence of tearing at the end during transfer, and ensuring high productivity and quality.

[0372] The functional layer constituting the long film of the present invention may include other layers other than the liquid crystal cured material layer and the alignment film. As such other layers, for example, cured resin layers such as a protective layer and a hard coat layer, and adhesive layers for bonding functional layers such as a liquid crystal cured material layer to other components such as a polarizing film, etc. may be cited. In addition, multiple liquid crystal cured material layers with different orientation directions and multiple alignment films with different orientation control forces may be included.

[0373] When the cured resin layer is included, the thickness thereof is 0.1 to 10 μm, preferably 0.5 to 5 μm, from the viewpoint of reducing the thickness of the entire functional layer.

[0374] The cured resin layer can be, for example, a film of cycloolefin polymer (COP), polyethylene terephthalate (PET), cellulose triacetate (TAC), etc., or a cured resin layer formed by curing a cured resin layer composition comprising a polymerizable monomer. From the viewpoint of thin filmization, it is preferred that the cured resin layer is formed by curing a cured resin layer of a composition. The cured resin layer can include multiple layers, but from the viewpoint of productivity, it is preferably less than 2 layers, more preferably a monolayer. In addition, the cured resin layer is preferably optically isotropic. If the cured resin layer is optically isotropic, when combined with a liquid crystal cured material layer, it is not easy to affect the optical properties of the liquid crystal cured material layer, and a functional layer with high optical properties can be obtained.

[0375] It should be noted that in this specification, there are cases where the functional group with the largest number of polymerizable groups contained in the composition for forming a cured resin layer used to form the cured resin layer is collectively referred to as a resin. That is, for example, when the number of acryloxy groups is the largest among the polymerizable groups contained in the composition for forming a cured resin layer, it is sometimes called an acrylic resin, and when the number of epoxy groups is the largest, it is sometimes called an epoxy resin, etc.

[0376] The cured resin layer preferably includes at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, polyurethane resin and melamine resin. By including at least one resin selected from the above resins, the curability is high and the reliability when combined with the cured layer of the polymerizable liquid crystal compound is easily improved.

[0377] The composition for forming a cured resin layer constituting the cured resin layer is a composition containing a polymerizable monomer capable of curing, such as a free radical polymerizable monomer, a cationic polymerizable monomer, a thermal polymerizable monomer, as a curable compound. From the perspective of high reaction speed, improved productivity, and easy improvement in reliability when combined with a cured layer of a polymerizable liquid crystal compound, it is more preferable to contain a free radical polymerizable monomer or a cationic polymerizable monomer.

[0378] As free radical polymerizable monomers suitable for forming the above-mentioned cured resin layer, for example, (meth)acrylate compounds such as multifunctional (meth)acrylate compounds; carbamate (meth)acrylate compounds such as multifunctional carbamate (meth)acrylate compounds; epoxy (meth)acrylate compounds such as multifunctional epoxy (meth)acrylate compounds; carboxyl-modified epoxy (meth)acrylate compounds, polyester (meth)acrylate compounds, etc. These can be used alone or in combination of two or more. Among them, as a polymerizable monomer, from the viewpoint of improving the reliability when combined with the cured layer of the polymerizable liquid crystal compound, the viewpoint of improving the adhesion with the adjacent layer, and the viewpoint of improving productivity, it is preferred to include a polymerizable monomer having a (meth)acryloyloxy group, more preferably to include a multifunctional (meth)acrylate compound, and particularly preferably to include a multifunctional acrylate compound.

[0379] The multifunctional (meth)acrylate compound refers to a compound having two or more (meth)acryloyl groups, preferably (meth)acryloyloxy groups, in the molecule, and examples thereof include a bifunctional (meth)acrylate monomer having two (meth)acryloyloxy groups in the molecule, a trifunctional or higher (meth)acrylate monomer having three or more (meth)acryloyloxy groups in the molecule, etc. It should be noted that in this specification, the term "(meth)acrylate" refers to "acrylate" or "methacrylate", and similarly, the term "(meth)acryloyl group" also refers to "acryloyl group" or "methacryloyl group".

[0380] The multifunctional (meth)acrylate compound may include one or more multifunctional (meth)acrylate compounds. In addition, when including two or more multifunctional (meth)acrylate compounds, the number of (meth)acryloyl groups may be the same or different between the multifunctional (meth)acrylate compounds.

[0381] Examples of the bifunctional (meth)acrylate monomer include alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate. di(meth)acrylates of aliphatic polyols such as trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, and pentaerythritol di(meth)acrylate; di(meth)acrylates of hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, and the like; Di(meth)acrylate of dicyclopentadiene or tricyclodecanediol; di(meth)acrylate of dioxanediol or dioxanediol such as 1,3-dioxane-2,5-diyl di(meth)acrylate [alias: dioxanediol di(meth)acrylate]; di(meth)acrylate of bisphenol A or bisphenol F ethylene oxide adduct such as bisphenol A ethylene oxide adduct diacrylate and bisphenol F ethylene oxide adduct diacrylate; acrylic acid adduct of bisphenol A diglycidyl ether and acrylic acid adduct of bisphenol F diglycidyl ether Epoxy di(meth)acrylate of bisphenol A or bisphenol F; polysiloxane di(meth)acrylate; di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester; 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane; 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane; di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane]; tris(hydroxyethyl)isocyanurate di(meth)acrylate, etc.

[0382] The trifunctional (meth)acrylate monomer is a monomer having three (meth)acryloyl groups, preferably (meth)acryloyloxy groups, in the molecule, and examples thereof include glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, a reaction product of pentaerythritol tri(meth)acrylate and anhydride, caprolactone-modified trimethylolpropane tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, epoxy Ethane-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified pentaerythritol tri(meth)acrylate, isocyanurate tri(meth)acrylate, a reaction product of caprolactone-modified pentaerythritol tri(meth)acrylate and an acid anhydride, a reaction product of ethylene oxide-modified pentaerythritol tri(meth)acrylate and an acid anhydride, a reaction product of propylene oxide-modified pentaerythritol tri(meth)acrylate and an acid anhydride, and the like.

[0383] The tetrafunctional (meth)acrylate monomer is a monomer having four (meth)acryloyl groups, preferably (meth)acryloyloxy groups, in the molecule, and examples thereof include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tripentaerythritol tetra(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, caprolactone-modified tripentaerythritol tetra(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified tripentaerythritol tetra(meth)acrylate, propylene oxide-modified pentaerythritol tetra(meth)acrylate, and propylene oxide-modified tripentaerythritol tetra(meth)acrylate.

[0384] Examples of the pentafunctional (meth)acrylate monomer include dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate, a reaction product of dipentaerythritol penta(meth)acrylate and an acid anhydride, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified tripentaerythritol penta(meth)acrylate, propylene oxide-modified dipentaerythritol penta(meth)acrylate, propylene oxide-modified tripentaerythritol penta(meth)acrylate, a reaction product of caprolactone-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, a reaction product of ethylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, and a reaction product of propylene oxide-modified dipentaerythritol penta(meth)acrylate and an acid anhydride.

[0385] Examples of the hexafunctional (meth)acrylate monomer include dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified tripentaerythritol hexa(meth)acrylate, propylene oxide-modified dipentaerythritol hexa(meth)acrylate, and propylene oxide-modified tripentaerythritol hexa(meth)acrylate.

[0386] Examples of the heptafunctional (meth)acrylate monomer include tripentaerythritol hepta(meth)acrylate, a reaction product of tripentaerythritol hepta(meth)acrylate and an acid anhydride, caprolactone-modified tripentaerythritol hepta(meth)acrylate, a reaction product of caprolactone-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, ethylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of ethylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, propylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of propylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, and the like.

[0387] The octafunctional (meth)acrylate monomer is a monomer having 8 (meth)acryloyl groups, preferably (meth)acryloyloxy groups, in the molecule, and examples thereof include tripentaerythritol octa(meth)acrylate, caprolactone-modified tripentaerythritol octa(meth)acrylate, ethylene oxide-modified tripentaerythritol octa(meth)acrylate, and propylene oxide-modified tripentaerythritol octa(meth)acrylate.

[0388] Examples of the cationically polymerizable monomer suitable for forming the cured resin layer include epoxy compounds having an epoxy group and oxetane compounds having an oxetane group.

[0389] The epoxy compound is a polymerizable monomer having at least one epoxy group in the molecule, and examples thereof include alicyclic epoxy compounds, aromatic epoxy compounds, and aliphatic epoxy compounds.

[0390] Alicyclic epoxy compounds are compounds having at least one epoxy group directly bonded to an alicyclic ring in the molecule. For example, 3,4-epoxycyclohexanecarboxylic acid 3,4-epoxycyclohexylmethyl ester, 3,4-epoxy-6-methylcyclohexanecarboxylic acid 3,4-epoxy-6-methylcyclohexanemethyl ester, ethylene bis(3,4-epoxycyclohexanecarboxylate), adipate bis(3,4-epoxycyclohexylmethyl) ester, adipate bis(3,4-epoxy-6-methylcyclohexylmethyl) ester, diethylene glycol bis(3,4-epoxycyclohexyl methyl ether), ethylene glycol bis(3,4-epoxycyclohexyl methyl) ether, etc. can be cited. These alicyclic epoxy compounds can be used alone or in combination of two or more.

[0391] Aromatic epoxy compounds are compounds having an aromatic ring and an epoxy group in the molecule. Specific examples thereof include bisphenol-type epoxy compounds or oligomers thereof such as diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and diglycidyl ether of bisphenol S; Novolac-type epoxy resins such as phenol Novolac epoxy resin, cresol Novolac epoxy resin, and hydroxybenzaldehyde phenol Novolac epoxy resin; polyfunctional epoxy compounds such as glycidyl ether of 2,2',4,4'-tetrahydroxydiphenylmethane and glycidyl ether of 2,2',4,4'-tetrahydroxybenzophenone; and polyfunctional epoxy resins such as epoxidized polyvinylphenol. These aromatic epoxy compounds can be used alone or in combination of two or more.

[0392] As for the hydrogenated epoxy compound, the nuclear hydrogenation product of the above-mentioned aromatic epoxy compound becomes the hydrogenated epoxy compound. These can be produced by the following method: in the presence of a catalyst and under pressure, an aromatic polyhydroxy compound, typically bisphenols, which is a raw material of the corresponding aromatic epoxy compound is selectively subjected to a hydrogenation reaction, and the polyol thus obtained, typically hydrogenated bisphenols, is used as a raw material, and is reacted with epichlorohydrin to form a chlorohydrin ether, and then an alkali is used to perform intramolecular ring closure. These hydrogenated epoxy compounds can be used alone or in combination of two or more.

[0393] Aliphatic epoxy compounds include polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts thereof. Specific examples thereof include diglycidyl ether of neopentyl glycol, diglycidyl ether of 1,4-butanediol, diglycidyl ether of 1,6-hexanediol, triglycidyl ether of glycerol, triglycidyl ether of trimethylolpropane, diglycidyl ether of polyethylene glycol, diglycidyl ether of propylene glycol, polyglycidyl ether of polyether polyols obtained by adding one or more alkylene oxides (ethylene oxide, propylene oxide) to aliphatic polyols such as ethylene glycol, propylene glycol, and glycerol. These aliphatic epoxy compounds can be used alone or in combination of two or more.

[0394] The oxetane compound is a compound containing at least one oxetane group in the molecule, and specific examples thereof include 3-ethyl-3-hydroxymethyloxetane (also referred to as oxetanol), 2-ethylhexyloxetane, 1,4-bis[{(3-ethyloxetane-3-yl)methoxy}methyl]benzene (also referred to as xylylenebisoxetane), 3-ethyl-3[{(3-ethyloxetane-3-yl)methoxy}methyl]oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-(cyclohexyloxy)methyl-3-ethyloxetane.

[0395] Examples of heat-polymerizable monomers suitable for forming a cured resin layer include melamine compounds. Examples of melamine compounds include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexabutoxymethylmelamine, etc. The melamine compounds may be used alone or in combination of two or more.

[0396] In addition, as other polymerizable monomers, a combination of an isocyanate compound and an alcohol compound having a hydroxyl group in the molecule can be cited, and polyurethane resin can be manufactured. The isocyanate compound used in the manufacture of polyurethane resin and urea resin usually has more than 2 isocyanate groups (-NCO) in the molecule, and various diisocyanates of aromatic, aliphatic or alicyclic can be used. As a specific example, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-toluene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-diphenyl diisocyanate, xylene diisocyanate, trimethyl hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and the nuclear hydrogenation of diisocyanates with aromatic rings in these can be cited. In addition, the alcohol compound used for the polyurethane resin generally has two or more hydroxyl groups in the molecule, and examples thereof include ethylene glycol, propylene glycol, 1,3-propanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, 2,2,4-trimethyl-1,3-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol ester of hydroxypivalic acid, 1,4-cyclohexanediol, spirodiol, tricyclodecane dimethanol, bisphenol A, hydrogenated bisphenol A, trimethylolethane, trimethylolpropane, glycerol, 3-methylpentane-1,3,5-triol, pentaerythritol, dipentaerythritol, tripentaerythritol, and glucose.

[0397] The above-mentioned polymerizable monomer can be appropriately selected from the viewpoint of curling caused by heating during and after curing, the viewpoint of improving processing characteristics, the viewpoint of adjusting the adhesion with substrate film and liquid crystal cured material layer, the viewpoint of improving productivity, the viewpoint of improving solvent resistance, and the viewpoint of improving reliability when combined with liquid crystal cured material layer. In the present invention, the cured resin layer preferably includes at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, polyurethane resin and melamine resin. In addition, for example, more than two kinds of free radical polymerizable monomers can be used, and free radical polymerizable monomers can also be combined with cationic polymerizable monomers. Especially from the viewpoint of improving productivity, it is preferred to contain free radical polymerizable monomers.

[0398] In addition to the above-mentioned polymerizable monomers, the composition for forming a cured resin layer may further contain additives such as a photopolymerization initiator, a thermal polymerization initiator, a solvent, an antioxidant, a photosensitizer, a leveling agent, an antioxidant, a chain transfer agent, a light stabilizer, a tackifier, a filler, a flow regulator, a plasticizer, a defoamer, a pigment, an antistatic agent, and an ultraviolet absorber. These additives are usually about 0.1 to 15% by mass relative to the mass of the solid content of the composition for forming a cured resin layer. It should be noted that in this specification, the so-called solid content, when the composition for forming a cured resin layer contains a solvent, refers to the total amount of the components remaining after removing the solvent from the composition.

[0399] In the composition for forming a cured resin layer, the content of the polymerizable monomer is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, relative to 100 parts by mass of the solid content of the composition. When it is within the above range, it is easy to improve the reliability when combined with the liquid crystal cured layer.

[0400] The composition for forming the above-mentioned cured resin layer preferably contains a polymerization initiator. As the polymerization initiator, photopolymerization initiators, thermal polymerization initiators, etc. can be mentioned. From the viewpoint of improving productivity, photopolymerization initiators are preferably used. Photopolymerization initiators are not particularly limited as long as they are substances that can initiate the curing of polymerizable monomers by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams. Photopolymerization initiators and photocationic polymerization initiators can be appropriately used according to the type of polymerizable monomer. As photoradical polymerization initiators and photocationic polymerization initiators, specifically, the same substances as the polymerization initiators exemplified in the above text as polymerization initiators that can be matched in the polymerizable liquid crystal composition that forms the liquid crystal cured material layer can be mentioned.

[0401] When the composition for forming a cured resin layer contains a polymerization initiator, the content thereof is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, relative to 100 parts by mass of the total amount of the curable compound. When the content of the polymerization initiator is above the lower limit, the polymerization initiation ability is fully exhibited, and when the content of the polymerization initiator is below the upper limit, the polymerization initiator is not likely to remain.

[0402] When the composition for forming a cured resin layer includes a solvent, it can be appropriately selected based on the viewpoint of fully dissolving the polymerizable monomer, polymerization initiator, etc. added to the composition for forming a cured resin layer, and the viewpoint of not dissolving the substrate film. For example, a solvent that can be used in the polymerizable liquid crystal composition described above can be used. Relative to the total amount of 100 parts by mass of the components included in the composition for forming a cured resin layer, the content of the solvent can be 1 to 10,000 parts by mass, preferably 10 to 1,000 parts by mass, and more preferably about 20 to 500 parts by mass.

[0403] In the present invention, as long as the composition of the functional layer includes a liquid crystal curing material layer and does not affect the effect of the present invention, it is not particularly limited. In the case where other layers such as an alignment film and a cured resin layer are also included in addition to the liquid crystal curing material layer, the stacking order of each layer can be appropriately selected. In the case where the functional layer includes a liquid crystal curing material layer, an alignment film and a cured resin layer, it is preferred that the liquid crystal curing material layer, the alignment film, and the cured resin layer exist adjacent to each other in sequence. When each layer is stacked in such an order, even if there is an uncured polymerizable liquid crystal compound in the liquid crystal curing material layer, especially in the liquid crystal curing material layer, the deep part (alignment film side) of the liquid crystal curing material layer where sufficient light is difficult to reach when the layer is cured, the diffusion of the uncured polymerizable liquid crystal compound can be prevented by the cured resin layer. After the functional layer is peeled off from the substrate film and transferred to other components, the diffusion of the uncured polymerizable liquid crystal compound to other components can be prevented by the cured resin layer. Thus, in the phase difference plate and elliptically polarizing plate of the functional layer transferred from the long film of the present invention, it is possible to effectively suppress the diffusion of the uncured polymerizable liquid crystal compound contained in the liquid crystal curing material layer, etc., to the layer (especially the adhesive layer) close to or adjacent to the liquid crystal curing material layer. Therefore, in a preferred embodiment of the present invention, the functional layer also includes an adhesive layer, which is stacked with other optical films (for example, polarizing films, etc.) via an adhesive layer. As such a functional layer, it is preferred that a liquid crystal curing material layer, an orientation film, and a cured resin layer exist adjacent to each other in sequence, and the adhesive layer can be arranged on the liquid crystal curing material layer side, or on the cured resin layer side.

[0404] When the functional layer constituting the long film of the present invention includes a cured resin layer, the cured resin layer can be obtained, for example, by applying a cured resin layer-forming composition as described above onto a substrate film, and if it contains a solvent, drying and removing the solvent to cure the polymerizable monomer.

[0405] As a method for applying the composition for forming a cured resin layer on the base film, the same method as the method exemplified above as the method for applying the polymerizable liquid crystal composition on the base film and the like can be mentioned.

[0406] When the composition for forming a cured resin layer contains a solvent, examples of a method for removing the solvent by drying include natural drying, ventilation drying, heating drying, and reduced pressure drying.

[0407] In the present invention, when the functional layer includes an adhesive layer, as the adhesive constituting the functional layer, for example, a pressure-sensitive adhesive, a drying-curing adhesive, and a chemical reaction adhesive can be cited. As a chemical reaction adhesive, for example, an active energy ray-curing adhesive can be cited. It should be noted that the adhesive layer can be provided as a constituent layer of the functional layer of the long film of the present invention, or it can be provided on the peeling surface after the substrate film is peeled off from the long film of the present invention.

[0408] Pressure-sensitive adhesives usually contain polymers and may contain solvents. Examples of polymers include acrylic polymers, silicone polymers, polyesters, polyurethanes, and polyethers. Among them, acrylic adhesives containing acrylic polymers have excellent optical transparency, appropriate wettability and cohesive force, excellent adhesion, high weather resistance, heat resistance, etc., and are not prone to floating or peeling under heating or humidification conditions, so they are preferred.

[0409] Preferred acrylic polymers include copolymers of (meth)acrylates in which the alkyl group in the ester portion is an alkyl group having 1 to 20 carbon atoms such as methyl, ethyl or butyl, and (meth)acrylic acid, hydroxyethyl (meth)acrylate and other (meth)acrylic acid monomers having a functional group.

[0410] The pressure-sensitive adhesive containing such a copolymer has excellent adhesiveness and can be removed relatively easily without leaving adhesive residue on the transfer object even when it is removed after being attached to the transfer object, so it is preferred. The glass transition temperature of the acrylic polymer is preferably 25°C or less, more preferably 0°C or less. The mass average molecular weight of such an acrylic polymer is preferably 100,000 or more.

[0411] As the solvent, solvents listed as solvents that can be used in polymerizable liquid crystal compositions and the like can be cited. The pressure-sensitive adhesive may contain a light diffusing agent. The light diffusing agent is an additive that imparts light diffusivity to the adhesive, and is preferably microparticles having a refractive index different from the refractive index of the polymer contained in the adhesive. As the light diffusing agent, microparticles containing inorganic compounds and microparticles containing organic compounds (polymers) can be cited. Most polymers contained as active ingredients of the adhesive, including acrylic polymers, have a refractive index of about 1.4 to 1.6, so it is preferably selected from light diffusing agents having a refractive index of 1.2 to 1.8. The refractive index difference between the polymer contained as an active ingredient of the adhesive and the light diffusing agent is usually 0.01 or more, and is preferably 0.01 to 0.2 from the viewpoint of the brightness and display properties of the display device. The microparticles used as the light diffusing agent are preferably spherical and nearly monodisperse microparticles, and more preferably microparticles with an average particle size of 2 to 6 μm. The refractive index is measured by the usual minimum deviation angle method or Abbe refractometer.

[0412] As microparticles containing inorganic compounds, aluminum oxide (refractive index 1.76) and silicon oxide (refractive index 1.45) can be cited. As microparticles containing organic compounds (polymers), melamine beads (refractive index 1.57), polymethyl methacrylate beads (refractive index 1.49), methyl methacrylate / styrene copolymer resin beads (refractive index 1.50-1.59), polycarbonate beads (refractive index 1.55), polyethylene beads (refractive index 1.53), polystyrene beads (refractive index 1.6), polyvinyl chloride beads (refractive index 1.46), and silicone resin beads (refractive index 1.46) can be cited. The content of the light diffusing agent is usually 3 to 30 parts by mass relative to 100 parts by mass of the polymer.

[0413] The thickness of the pressure-sensitive adhesive is determined according to its adhesion, etc., so there is no particular restriction, and it is usually 1 to 40 μm. From the perspective of processability, durability, etc., the thickness is preferably 3 to 25 μm, and more preferably 5 to 20 μm. By making the thickness of the adhesive layer formed by the adhesive 5 to 20 μm, it is possible to ensure the brightness when looking at the display device (which has an optical film including the functional layer transferred from the long film of the present invention) from the front and when looking at the display device from an oblique direction, and it is not easy to produce stains and blurs on the displayed image.

[0414] The dry curing adhesive may contain a solvent. As the dry curing adhesive, there can be mentioned a polymer containing a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group, or a composition containing a polyurethane resin as a main component, and a crosslinking agent or curable compound such as a polyaldehyde, an epoxy compound, an epoxy resin, a melamine compound, a zirconium oxide compound, and a zinc compound. As the polymer of a monomer having a protic functional group such as a hydroxyl group, a carboxyl group or an amino group and an ethylenically unsaturated group, there can be mentioned ethylene-maleic acid copolymers, itaconic acid copolymers, acrylic acid copolymers, acrylamide copolymers, saponified products of polyvinyl acetate, and polyvinyl alcohol resins.

[0415] Examples of the polyvinyl alcohol resin include polyvinyl alcohol, partially saponified polyvinyl alcohol, completely saponified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol. The content of the polyvinyl alcohol resin in the water-based binder is usually 1 to 10 parts by mass, preferably 1 to 5 parts by mass, relative to 100 parts by mass of water.

[0416] Examples of the polyurethane resin include polyester-based ionomer-type polyurethane resins and the like.

[0417] The polyester ionomer polyurethane resin referred to herein is a polyurethane resin having a polyester skeleton and into which a small amount of ionic components (hydrophilic components) are introduced. The ionomer polyurethane resin is emulsified in water without using an emulsifier to form an emulsion, so it can be made into a water-based adhesive. When using the polyester ionomer polyurethane resin, it is effective to add a water-soluble epoxy compound as a crosslinking agent.

[0418] As epoxy resin, polyamide polyamine (polyamidepolyamine) obtained by the reaction of polyalkylene polyamines such as diethylenetriamine or triethylenetetramine with dicarboxylic acids such as adipic acid, polyamide epoxy resin obtained by reacting with epichlorohydrin, etc. can be cited. As commercial products of the polyamide epoxy resin, "SUMIREZRESIN (registered trademark) 650" and "SUMIREZRESIN 675" (the above are made by Sumika Chemtex Co., Ltd.), "WS-525" (made by Japan PMC Co., Ltd.) can be cited. When the epoxy resin is added, the amount thereof added is usually 1 to 100 parts by mass, preferably 1 to 50 parts by mass, relative to 100 parts by mass of the polyvinyl alcohol-based resin.

[0419] The thickness of the adhesive layer formed of a drying-curing adhesive is usually 0.001 to 5 μm, preferably 0.01 to 2 μm, and more preferably 0.01 to 0.5 μm. If the adhesive layer formed of a drying-curing adhesive is too thick, the appearance is likely to be poor.

[0420] The active energy ray-curable adhesive may contain a solvent. The active energy ray-curable adhesive refers to an adhesive that is cured by irradiation with active energy rays. Examples of the active energy ray-curable adhesive include a cationically polymerizable adhesive containing an epoxy compound and a cationic polymerization initiator, a radically polymerizable adhesive containing an acrylic curing component and a radical polymerization initiator, an adhesive containing both a cationically polymerizable curing component such as an epoxy compound and a radically polymerizable curing component such as an acrylic compound and further containing a cationic polymerization initiator and a radical polymerization initiator, and an adhesive that does not contain these polymerization initiators and is cured by irradiation with electron rays.

[0421] Among them, free radical polymerizable active energy ray-curable adhesives containing acrylic curing components and photo-free radical polymerization initiators, and cationic polymerizable active energy ray-curable adhesives containing epoxy compounds and photo-cationic polymerization initiators are preferred. As acrylic curing components, (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate and (meth)acrylic acid can be cited. The active energy ray-curable adhesive containing epoxy compounds can also contain compounds other than epoxy compounds. As compounds other than epoxy compounds, oxetane compounds, acrylic compounds, etc. can be cited.

[0422] As the photo radical polymerization initiator and the photo cationic polymerization initiator, the same polymerization initiator as exemplified as the polymerization initiator that can be used in the polymerizable liquid crystal composition can be cited. The content of the radical polymerization initiator and the cationic polymerization initiator is usually 0.5 to 20 parts by mass, preferably 1 to 15 parts by mass, relative to 100 parts by mass of the active energy ray-curable adhesive.

[0423] The active energy ray-curable adhesive may further contain an ion scavenger, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow regulator, a plasticizer, a defoaming agent, and the like.

[0424] As active energy rays, visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays and electron rays can be cited, preferably ultraviolet rays and electron rays. Preferred ultraviolet irradiation conditions are the same as the curing conditions of the polymerizable liquid crystal composition when forming the liquid crystal cured layer.

[0425] As for the strip film of the present invention, when the functional layer is peeled off from the substrate film and transferred to other optical films using a roll-to-roll method, it is easy to make the functional layer peeled off linearly relative to the peeling direction (long side direction), and the tearing and detachment at the end of the functional layer after transfer are suppressed during transfer. Thus, the functional layer can be transferred with good productivity under the state of maintaining the optical properties of the functional layer possessed by the strip film, and therefore, it can be suitably used for the manufacture of optical laminates such as phase difference plates and elliptically polarizing plates requiring high optical properties.

[0426] For example, an elliptically polarizing plate can be prepared by peeling off the substrate film from the long film of the present invention having a functional layer including a liquid crystal cured layer satisfying the above formulas (1) and (2) or (3) and (4), and transferring the functional layer to a polarizing film. In this case, the functional layer and the polarizing film can be bonded via an adhesive layer as needed.

[0427] The polarizing film includes a film having a polarizing function, a stretched film adsorbed with a dye having absorption anisotropy, a film including a film coated with a dye having absorption anisotropy as a polarizer, etc. As the dye having absorption anisotropy, for example, a dichroic dye can be mentioned.

[0428] For a film that includes a stretched film adsorbed with a dye having absorption anisotropy as a polarizer, it is usually made by clamping a transparent protective film with an adhesive on at least one side of the following polarizer, and the polarizer is manufactured through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic dye so that it adsorbs the dichroic dye; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic dye with an aqueous boric acid solution; and a step of washing with water after the treatment with the aqueous boric acid solution.

[0429] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0430] The saponification degree of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.

[0431] The film made of such a polyvinyl alcohol resin can be used as a raw film of a polarizing film. The method of making a polyvinyl alcohol resin into a film is not particularly limited, and the film can be made by a known method. The film thickness of the polyvinyl alcohol raw film can be, for example, about 10 to 150 μm.

[0432] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in multiple stages thereof. When the uniaxial stretching is performed, the uniaxial stretching can be performed between rollers having different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen with a solvent. The stretching ratio is usually about 3 to 8 times.

[0433] The polyvinyl alcohol-based resin film can be dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.

[0434] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As the dichroic organic dyes, dichroic direct dyes formed by disazo compounds such as CI Direct Red (DIRECT RED) 39, and dichroic direct dyes formed by compounds such as triazo and tetrakis azo can be cited. For the polyvinyl alcohol-based resin film, it is preferably immersed in water before dyeing.

[0435] When iodine is used as the dichroic dye, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing iodine and potassium iodide can generally be employed.

[0436] The content of iodine in the aqueous solution is usually about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is usually about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 20 to 1,800 seconds.

[0437] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye can generally be employed.

[0438] The content of the dichroic organic dye in the aqueous solution is usually 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.

[0439] Boric acid treatment after dyeing based on dichroic pigments can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution of boric acid. The content of boric acid in the aqueous solution of boric acid is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as a dichroic pigment, the aqueous solution of boric acid preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous solution of boric acid is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0440] The polyvinyl alcohol-based resin film treated with boric acid may be washed with water. The washing may be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of water in the washing may be generally about 5 to 40°C.

[0441] In addition, the immersion time is usually about 1 to 120 seconds.

[0442] A drying process can be performed after washing to obtain a polarizer. The drying process can be performed, for example, using a hot air dryer or a far infrared heater. The temperature of the drying process is usually about 30 to 100° C., preferably 50 to 80° C. The time of the drying process is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying, the moisture content of the polarizer can be reduced to a practical level. Its moisture content is usually about 5 to 20% by mass, preferably 8 to 15% by mass. When the moisture content is within the above range, a polarizer with moderate flexibility and good thermal stability can be obtained.

[0443] The thickness of the polarizer obtained by uniaxially stretching the polyvinyl alcohol-based resin film, dyeing it with a dichroic dye, treating it with boric acid, washing it with water, and drying it as described above is preferably 5 to 40 μm.

[0444] As the film formed by coating with anisotropic pigment, coating comprising a composition having a dichroic pigment with liquid crystal or a composition comprising a dichroic pigment and polymerizable liquid crystal and the like can be enumerated. The film preferably has a protective film on one or both sides. As the protective film, the film identical with the substrate film exemplified in the foregoing can be enumerated.

[0445] The film formed by coating the dye having absorption anisotropy is preferably as thin as possible, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0446] Specific examples of the film formed by coating a dye having absorption anisotropy include films described in JP-A-2012-33249 and the like.

[0447] A polarizing film can be obtained by laminating a transparent protective film on at least one side of the polarizer obtained as described above via an adhesive. As the transparent protective film, the same transparent film as the substrate film exemplified above can be preferably used.

[0448] When the long strip film of the present invention includes a horizontally oriented liquid crystal cured layer as a functional layer, when the functional layer is transferred from the long strip film of the present invention to the polarizing film, the transfer is preferably performed in a manner such that the angle formed by the slow axis (optical axis) of the horizontally oriented liquid crystal cured layer constituting the functional layer and the absorption axis of the polarizing film becomes 45±5°.

[0449] An optical laminate such as an elliptically polarizing plate including a functional layer transferred from the long film of the present invention can be used in various display devices.

[0450] The so-called display device is a device having a display element, including a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (such as field emission display devices (FED), surface field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements, plasma display devices, projection display devices (such as grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)) and piezoelectric ceramic displays. Liquid crystal display devices include transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, and semi-transmissive liquid crystal display devices. Any one of a liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, the elliptically polarizing plate comprising a functional layer transferred from the long film of the present invention can be suitably used in organic electroluminescent (EL) display devices and inorganic electroluminescent (EL) display devices, and can also be suitably used in liquid crystal display devices and touch panel display devices. These display devices can present good image display characteristics by having an elliptically polarizing plate with high reliability.

[0451] Example

[0452] Hereinafter, the present invention will be described in more detail using Examples. It should be noted that, unless otherwise specified, "%" and "parts" in Examples refer to mass % and mass parts, respectively.

[0453] 1. Example 1

[0454] (1) Preparation of Composition for Forming Horizontal Alignment Film (A1)

[0455] 5 parts of a photo-alignment material having the following structure (weight average molecular weight: 30,000) and 95 parts of cyclopentanone (solvent) were mixed as components, and the obtained mixture was stirred at 80° C. for 1 hour to obtain a composition (A1) for forming a horizontal alignment film.

[0456]

[0457] (2) Preparation of polymerizable liquid crystal compounds

[0458] In order to be used in the formation of a horizontally aligned liquid crystal cured film, a polymerizable liquid crystal compound (X1) and a polymerizable liquid crystal compound (Y1) having the following molecular structures are prepared respectively. The polymerizable liquid crystal compound (X1) is manufactured according to the method described in Japanese Patent Publication No. 2010-31223. In addition, the polymerizable liquid crystal compound (Y1) is manufactured according to the method described in Japanese Patent Publication No. 2009-173893.

[0459] Polymerizable liquid crystal compound (X1)

[0460]

[0461] Polymerizable liquid crystal compound (Y1)

[0462]

[0463] (3) Preparation of polymerizable liquid crystal composition (B1)

[0464] The polymerizable liquid crystal compound (X1) and the polymerizable liquid crystal compound (Y1) are mixed in a mass ratio of 90:10 to obtain a mixture. With respect to 100 parts by mass of the obtained mixture, 0.10 parts by mass of a leveling agent "BYK-361N" (manufactured by BYK-Chemie), 0.25 parts by mass of a leveling agent "F-556" (manufactured by DIC Corporation), and 3 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone ("Irgacure (registered trademark) 369 (Irg369)" manufactured by BASF JAPAN Co., Ltd.) as a photopolymerization initiator and 7.5 parts by mass of "Irgacure OXE-03" manufactured by BASF JAPAN Co., Ltd. are added. Furthermore, cyclopentanone is added in such a manner that the solid content concentration becomes 13%. The mixture is stirred at 80°C for 1 hour to obtain a polymerizable liquid crystal composition (B1).

[0465] A 1 mg / 50 mL tetrahydrofuran solution of the polymerizable liquid crystal compound (X1) was prepared to obtain a sample for measurement. The sample for measurement was placed in a sample cell for measurement with an optical path length of 1 cm, and was set in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. Based on the obtained absorption spectrum, the wavelength with the maximum absorbance was read. As a result, the maximum absorption wavelength λ in the range of 300 to 400 nm was max is 350nm.

[0466] (4) Preparation of Liquid Crystal Cured Material Layer

[0467] By die coating, a triacetate cellulose film (KC4UY, manufactured by KONICA MINOLTA, INC.) having a concave-convex portion with a width of 15 mm in the short side direction (total width in the short side direction of 30 mm) was coated with a horizontal alignment film-forming composition (A1) in such a manner as to have a width shown as "functional layer coating width C" in Table 1, respectively, at both ends of the substrate. At this time, the coating was performed in such a manner that the ends of the coating film of the horizontal alignment film-forming composition (A1) were located 7.5 mm inside from both ends of the substrate film, and the concave-convex portions at both ends of the coating film were covered by 7.5 mm, respectively. Then, after heating and drying at 100°C for 2 minutes, 100 mJ (based on 313 nm) of polarized UV light was irradiated in such a manner that the direction of the orientation control force was at an angle of 45° relative to the long side direction of the above-mentioned film, and a horizontal alignment film was formed on the above-mentioned film. The film thickness of the obtained horizontal alignment film was measured by an ellipsometer, and the result was 0.2 μm. Next, the polymerizable liquid crystal composition (B1) was coated on the horizontal alignment film with the same width as the film by die coating so that the average film thickness of the coating film was 17 μm, and then heated and dried at 120° C. for 2 minutes. Then, ultraviolet rays were irradiated from the side coated with the polymerizable liquid crystal composition (B1) using an ultraviolet irradiation device (in a nitrogen atmosphere, the cumulative light amount at a wavelength of 365 nm: 500 mJ / cm 2 ), thereby obtaining a long film (length: 2000 m) consisting of a liquid crystal cured material layer / horizontal alignment film / base film. The obtained long film was wound around an FRP core having an inner diameter of 6 inches.

[0468] Within the range of the concave and convex parts without covering the ends, the average total thickness measured along the width direction of the long strip film of the substrate film / horizontally oriented film / liquid crystal curing material layer by a contact film thickness meter was subtracted from the average substrate thickness obtained by measuring the substrate film portion after peeling off the functional layer (formed by the horizontal oriented film and the liquid crystal curing material layer) at the same position in the width direction, and the average thickness X of the functional layer in the plane was confirmed, and the result was 2μm. In addition, similarly, the maximum height Y of the convex part obtained by measuring the ends of the long strip film at the same position in the width direction at a spacing of 1mm using a contact film thickness meter was 7μm. The wound long strip film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer.

[0469] (5) Evaluation of properties of long films

[0470] <Evaluation of peelability of functional layer>

[0471] A 25 μm pressure-sensitive adhesive manufactured by LINTEC was laminated so as to be 5 mm inward from the coated end of the functional layer, and a cellulose triacetate film (KC6UA) manufactured by Konica Minolta, Inc. was laminated thereon. The cellulose triacetate film was peeled off parallel to the long side direction to transfer the functional layer, and the peeling state of the functional layer on the substrate film side after the transfer was visually observed by reflection under a fluorescent lamp.

[0472] The case where the film was able to be peeled off in parallel with the long side direction and well was judged as 0, and the case where peeling failure such as serration occurred was judged as x. The results are shown in Table 2.

[0473] <Measurement of Substrate Peel Force>

[0474] The central part of the width direction of the long film formed by the functional layer and the substrate film was sampled, and after the liquid crystal cured material layer side was subjected to corona treatment, it was bonded to a glass of length 12cm×width 10cm×thickness 0.7mm (composition: substrate film / functional layer / adhesive layer / glass) via a 25μm pressure-sensitive adhesive manufactured by LINTEC. For the obtained sample, a 25mm wide incision was made from the substrate side using a cutting machine. The prepared sample was set in Autograph "EZ-L" manufactured by Shimadzu Corporation, and a 25mm wide substrate was peeled off at a speed of 300mm / minute in a direction parallel to the glass surface to confirm the peeling force at this time. The results are shown in Table 2.

[0475] <Measurement of Phase Difference Value of Liquid Crystal Cured Material Layer>

[0476] The liquid crystal cured material layer side of the long film formed by the substrate film, the horizontal alignment film, and the liquid crystal cured material layer was subjected to corona treatment, and was bonded to a glass of length 4 cm × width 4 cm × thickness 0.7 mm via a 25 μm pressure-sensitive adhesive manufactured by LINTEC, and then the substrate film was peeled off. KOBRA-WPR manufactured by Oji Instruments Co., Ltd. was used to measure Re (450) and Re (550) of the liquid crystal cured material layer, and α = Re (450) / Re (550) was calculated. The results are shown in Table 2.

[0477] 2. Example 2

[0478] (1) Preparation of Cured Resin Layer-Forming Composition (C1)

[0479] A solution was prepared by dissolving 50 parts of dipentaerythritol hexaacrylate (ARONIX M-403, multifunctional acrylate manufactured by Toagosei Co., Ltd.), 50 parts of an acrylate resin (Ebecryl 4858 manufactured by Daicel UCB Co., Ltd.), and 3 parts of 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropane-1-one (Irgacure 907; manufactured by Ciba Specialty Chemicals Co., Ltd.) in 250 parts of isopropyl alcohol to obtain a composition (C1) for forming a cured resin layer containing an acrylate compound.

[0480] (2) Preparation of Cured Resin Layer

[0481] The composition (C1) for forming a curable resin layer was applied to the cellulose triacetate film provided with the same concavo-convex portion as in Example 1 by die coating so as to have the width shown as "functional layer coating width C" in Table 1. At this time, the coating was performed so that the ends of the coating film of the composition (C1) for forming a curable resin layer were located 7.5 mm inside from both ends of the substrate film and 7.5 mm of the concavo-convex portions at both ends of the coating film were covered. Then, after drying at 60° C. for 1 minute, ultraviolet rays were irradiated from one side coated with the composition (C1) for forming a curable resin layer using an ultraviolet irradiation device (in a nitrogen atmosphere, the accumulated light amount at a wavelength of 365 nm: 400 mJ / cm 2 ), thereby forming a cured resin layer. At this time, the laminate of the triacetylcellulose film and the cured resin layer was separately measured for Re (550) using "KOBRA-WPR" manufactured by Oji Scientific Instruments Co., Ltd., and the result confirmed that the phase difference value was 5 nm or less, indicating optical isotropy.

[0482] Next, a horizontally oriented film and a liquid crystal cured material layer were formed on the obtained cured resin layer using the same method as in Example 1, thereby obtaining a 1000 m long strip film formed by a liquid crystal cured material layer / horizontally oriented film / cured resin layer / base material film. The obtained long strip film was wound on an FRP core with an inner diameter of 6 inches. The in-plane average thickness X of the functional layer formed by the cured resin layer / horizontally oriented film / liquid crystal cured material layer was confirmed to be 4 μm. In addition, the maximum height Y of the convex portion was 9 μm. The wound long strip film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0483] 3. Example 3

[0484] As a substrate film, a substrate COP film (ZF-14-50) manufactured by Zeon Co., Ltd. of Japan was used, and a heated embossing roller was pressed to set an embossing portion of 12.5 mm width at both ends of the substrate film, and a corona treatment was applied. Using a die coating method, a curing resin layer forming composition (C1) was applied to the substrate film in a manner to obtain a width shown as "functional layer coating width C" in Table 1. At this time, the coating was applied in a manner such that the end of the coating film of the curing resin layer forming composition (C1) was located 7.5 mm inside each end of the substrate film, and the concave and convex portions at both ends of the coating film were covered with 5 mm each. In addition, a long film was prepared in the same manner as in Example 2, and the average thickness X of the functional layer in the plane was confirmed, and the result was 4 μm. In addition, the maximum height Y of the convex portion was 8 μm. The wound long film was stored in an environment of 23 ° C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. Table 2 shows the results.

[0485] 4. Example 4

[0486] (1) Preparation of polymerizable liquid crystal composition (B2)

[0487] With respect to 100 parts by mass of the polymerizable liquid crystal compound (X2) prepared with reference to Japanese Patent Publication No. 2016-81035, 0.10 parts by mass of leveling agent "BYK-361N" (manufactured by BYK-Chemie), 0.25 parts by mass of leveling agent "F-556" (manufactured by DIC), 3 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (manufactured by BASF JAPAN Co., Ltd. "Irgacure (registered trademark) 369 (Irg369)") as a photopolymerization initiator, and 7.5 parts by mass of "Irgacure OXE-03" manufactured by BASF JAPAN Co., Ltd. were added. Furthermore, cyclopentanone was added in a manner such that the solid content concentration became 13%. The mixture was stirred at 80°C for 1 hour to obtain a polymerizable liquid crystal composition (B2).

[0488] A 1 mg / 50 mL tetrahydrofuran solution of the polymerizable liquid crystal compound (X2) was prepared to obtain a sample for measurement. The sample for measurement was placed in a sample cell with an optical path length of 1 cm, and placed in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. Based on the obtained absorption spectrum, the wavelength with the maximum absorbance was read. As a result, the maximum absorption wavelength λ in the range of 300 to 400 nm was max It is 352nm.

[0489] Polymerizable liquid crystal compound (X2)

[0490]

[0491] Except for using (B2) instead of the polymerizable liquid crystal composition (B1), a long film was prepared in the same manner as in Example 1. The average in-plane thickness X of the functional layer was confirmed to be 2 μm. In addition, the maximum height Y of the convex portion was 7 μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0492] 5. Example 5

[0493] (1) Preparation of polymerizable liquid crystal composition (B3)

[0494] With respect to 100 parts by mass of the polymerizable liquid crystal compound (X3) prepared with reference to International Patent Publication No. 2015 / 025793, 0.10 parts by mass of the leveling agent "BYK-361N" (manufactured by BYK-Chemie), 0.25 parts by mass of the leveling agent "F-556" (manufactured by DIC), 3 parts by mass of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (manufactured by BASF JAPAN Co., Ltd. "Irgacure (registered trademark) 369 (Irg369)") as a photopolymerization initiator, and 7.5 parts by mass of "Irgacure OXE-03" manufactured by BASF JAPAN Co., Ltd. were added. Furthermore, cyclopentanone was added in such a manner that the solid content concentration became 13%. The mixture was stirred at 80°C for 1 hour to obtain a polymerizable liquid crystal composition (B3).

[0495] A 1 mg / 50 mL tetrahydrofuran solution of the polymerizable liquid crystal compound (X3) was prepared to obtain a sample for measurement. The sample for measurement was placed in a sample cell with an optical path length of 1 cm, and placed in an ultraviolet-visible spectrophotometer ("UV-2450" manufactured by Shimadzu Corporation) to measure the absorption spectrum. The wavelength of maximum absorbance was read from the obtained absorption spectrum. The maximum absorption wavelength λ in the range of 300 to 400 nm was max It is 352nm.

[0496] Polymerizable liquid crystal compound (X3)

[0497]

[0498] Except for using (B3) instead of the polymerizable liquid crystal composition (B1), a long film was prepared in the same manner as in Example 1. The average in-plane thickness X of the functional layer was confirmed, and the result was 2 μm. In addition, the maximum height Y of the convex portion was 7 μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0499] 6. Example 6

[0500] (1) Preparation of polymerizable liquid crystal composition (B4)

[0501] Relative to 100 parts by mass of the liquid crystal compound LC242 represented by the following formula (LC242): Paliocolo RLC242 (registered trademark of BASF), 0.10 parts by mass of the leveling agent "BYK-361N" (manufactured by BYK-Chemie), 0.25 parts by mass of the leveling agent "F-556" (manufactured by DIC), and 3 parts by mass of the polymerization initiator Irg369 were added, and cyclopentanone was added in such a way that the solid content concentration became 13 parts by mass. The mixture was stirred at 80° C. for 1 hour to obtain a polymerizable liquid crystal composition (B4).

[0502] Polymerizable liquid crystal compound (LC242)

[0503] Liquid crystal compound LC242: Paliocolor LC242 (registered trademark of BASF)

[0504]

[0505] As a substrate film, a triacetyl cellulose film provided with a concavo-convex portion as in Example 1 was used, and a horizontal alignment film-forming composition (A1) was applied to the triacetyl cellulose film by die coating in a manner to obtain a width shown as "functional layer coating width C" in Table 1. At this time, the coating was performed in a manner such that the ends of the coating film of the horizontal alignment film-forming composition (A1) were located 7.5 mm inside each of the two ends of the substrate film, and the concavo-convex portions at both ends of the coating film were covered by 7.5 mm, respectively. Then, after heating and drying at 100°C for 2 minutes, 100 mJ (based on 313 nm) of polarized UV light was irradiated in a manner such that the direction of the orientation control force was at an angle of 15° relative to the long side direction of the above film, thereby forming a horizontal alignment film on the above film. The film thickness of the obtained horizontal alignment film was measured by an ellipsometer, and the result was 0.2 μm. Next, the polymerizable liquid crystal composition (B4) was coated on the horizontal alignment film with the same width as the film by die coating so that the average film thickness of the coating film was 17 μm, and then heated and dried at 80° C. for 1 minute. Then, ultraviolet rays were irradiated from the side coated with the polymerizable liquid crystal composition using an ultraviolet irradiation device (in a nitrogen atmosphere, the cumulative light amount at a wavelength of 365 nm: 500 mJ / cm 2 ), thereby obtaining a 500m long strip film formed by a liquid crystal curing layer / horizontally oriented film / substrate film. The obtained long strip film was wound on an FRP core with an inner diameter of 6 inches. The average in-plane thickness X of the functional layer was confirmed to be 2μm. In addition, the maximum height Y of the convex portion was 8μm. The wound long strip film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0506] 7. Example 7

[0507] (1) Preparation of vertically aligned polymerizable liquid crystal composition (B5)

[0508] A mixed solution of 13 parts by mass of "KBE-903" manufactured by Shin-Etsu Chemical Co., Ltd. and 87 parts by mass of cyclopentanone and a mixed solution of 13 parts by mass of "Karenz MOI-EG" manufactured by Showa Denko K.K. and 87 parts by mass of cyclopentanone were mixed so as to obtain KBE-903:Karenz MOI-EG=1.00:1.35 (mass ratio), and then kept warm at 30°C for 16 hours to obtain a mixed solution (hereinafter sometimes referred to as mixed solution (1)) containing the following compound (preliminary reaction compound), wherein the compound has a functional group (hydroxysilyl group) capable of reacting with a hydroxyl group or a carboxyl group and a (meth)acryloyl group (acryloyl group) in the molecule.

[0509] Next, the polymerizable liquid crystal compound (X1) and the polymerizable liquid crystal compound (Y1) were mixed at a mass ratio of 90:10 to obtain a mixture. To 100 parts by mass of the obtained mixture, 0.25 parts by mass of a leveling agent "F-556" (manufactured by DIC Corporation), 2.0 parts by mass of an ionic compound A (molecular weight: 645) prepared with reference to Japanese Patent Application No. 2016-514802, 6 parts by mass of Irgacure 369E (manufactured by BASF JAPAN Co., Ltd.) as a photopolymerization initiator, and 1.0 parts by mass of "APG-700" (bifunctional) manufactured by Shin-Nakamura Chemical Co., Ltd. as a polymerizable non-liquid crystal compound having two or more (meth)acryloyl groups were added, and cyclopentanone was added so that the solid content concentration became 13%. Furthermore, a compound (pre-reaction compound) having a functional group capable of reacting with a hydroxyl group or a carboxyl group and a (meth) acryloyl group in the molecule is added in an amount of 2.35 parts by mass relative to 100 parts by mass of the mixture of the polymerizable liquid crystal compounds (X1) and (Y1) to obtain a mixture. The obtained mixture is stirred at 80° C. for 1 hour to obtain a vertically aligned polymerizable liquid crystal composition (B5).

[0510] Ionic compound A:

[0511]

[0512] By die coating, a vertically oriented polymerizable liquid crystal composition (B5) was applied to a cellulose triacetate film (KC4UY, manufactured by KONICA MINOLTA, INC.) provided with the same concave and convex portions as in Example 1, in such a manner that the average film thickness of the coating film became 9.5 μm and the width shown as the "functional layer coating width C" in Table 1 was obtained. At this time, the coating was performed in such a manner that the ends of the coating film of the vertically oriented polymerizable liquid crystal composition (B5) were located 7.5 mm inside from both ends of the substrate film, and the concave and convex portions at both ends of the coating film were covered by 7.5 mm, respectively. Next, after heating and drying at 120°C for 90 seconds, ultraviolet rays were irradiated from one side coated with the polymerizable liquid crystal composition (B5) using an ultraviolet irradiation device (cumulative light amount at a wavelength of 365 nm under a nitrogen atmosphere: 500 mJ / cm 2 ), thereby obtaining a 1000m long film formed by a liquid crystal cured material layer / substrate film. The obtained long film was wound on an FRP core with an inner diameter of 6 inches. The average thickness X in the surface was confirmed to be 1μm. In addition, the maximum height Y of the convex portion was 6μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0513] <Rth measurement of vertically aligned liquid crystal cured layer>

[0514] The liquid crystal curing material layer side of the long film formed by the substrate film and the (vertical orientation) liquid crystal curing material layer prepared by the above steps is subjected to corona treatment, and after being bonded to a glass of length 4cm×width 4cm×thickness 0.7mm via a 25μm pressure-sensitive adhesive made by LINTEC, the substrate film is peeled off. For the obtained laminate formed by glass, adhesive, and liquid crystal curing material layer, KOBRA-WPR made by Prince Instruments Co., Ltd. is used to change the incident angle of light toward the sample for optical property measurement, and the front phase difference value and the phase difference value when tilted 40° with the leading axis as the center are measured. The average refractive index at each wavelength is measured using an ellipsometer M-220 made by JASCO Corporation. In addition, the film thickness uses the above-mentioned in-plane average thickness. The three-dimensional refractive index was calculated based on the above-mentioned front phase difference value, the phase difference value when tilted 40° around the phase axis, the average refractive index, and the film thickness, and with reference to the Oji Measurement Equipment Technical Data (http: / / www.oji-keisoku.co.jp / products / kobra / reference.html). Based on the obtained three-dimensional refractive index, the optical properties of each vertically aligned liquid crystal cured layer were calculated according to the following formula. The results are shown in Table 2.

[0515] RthC(λ)=((nxC(λ)+nyC(λ)) / 2-nzC(λ))×dC

[0516] It should be noted that RthC(λ) represents the phase difference value in the thickness direction of the vertically aligned liquid crystal cured layer at a wavelength of λnm. In addition, nxC(λ) represents the in-plane principal refractive index of the vertically aligned liquid crystal cured layer at a wavelength of λnm, nyC(λ) represents the refractive index in the direction orthogonal to nxC(λ) in the plane at a wavelength of λnm, nzC(λ) represents the refractive index in the thickness direction of the vertically aligned liquid crystal cured layer at a wavelength of λnm, and when nxC(λ)=nyC(λ), nxC(λ) can be set to the refractive index in any direction in the film plane, and dC represents the film thickness of the vertically aligned liquid crystal cured layer.

[0517] 8. Example 8

[0518] A cured resin layer was prepared on a cellulose triacetate film in the same manner as in Example 2, and a long film was prepared by the same method as in Example 7. The average thickness X of the functional layer in the plane was confirmed to be 3 μm. In addition, the maximum height Y of the convex portion was 8 μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the plane and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0519] 9. Example 9

[0520] As a substrate film, a substrate COP film (ZF-14-50) manufactured by Zeon Co., Ltd. of Japan was used, and a heated embossing roller was pressed to set an embossing portion of 12.5 mm width at both ends of the substrate film, and a corona treatment was applied. Using a die coating method, a curable resin layer-forming composition (C1) was applied to the substrate film in a manner that the width was shown as "functional layer coating width C" in Table 1. At this time, the coating was applied in a manner that the ends of the coating film of the curable resin layer-forming composition (C1) were located 7.5 mm inside each end of the substrate film, and the concave and convex portions at both ends of the coating film were covered with 5 mm each. In addition, the same operation as in Example 8 was performed to obtain a long film. The average in-plane thickness X of the functional layer was confirmed, and the result was 3 μm. In addition, the maximum height Y of the convex portion was 11 μm. The wound long film was stored at 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. Table 2 shows the results.

[0521] 10. Example 10

[0522] (1) Preparation of vertical alignment film-forming composition (A2)

[0523] A composition (A2) for forming a vertically oriented film was prepared by mixing 0.5% of polyimide ("Sunever SE-610" manufactured by Nissan Chemical Industries, Ltd.), 72.3% of N-methyl-2-pyrrolidone, 18.1% of 2-butoxyethanol, 9.1% of ethylcyclohexane, and 0.01% of DPHA (manufactured by Shin-Nakamura Chemical).

[0524] As a substrate film, a COP film provided with an embossed portion in the same manner as in Example 9 was used. Using a die coating method, a vertically oriented film-forming composition (A2) was applied on the COP film in a manner that the width was shown as the "functional layer coating width C" in Table 1. At this time, the coating was performed in a manner that the ends of the coating film of the vertically oriented film-forming composition (A2) were located 7.5 mm inward from each end of the substrate film, and the concave and convex portions at both ends of the coating film were covered by 5 mm, respectively. Heat and dry at 80°C for 1 minute to form a vertically oriented film on the above film. Next, using a die coating method, a polymerizable liquid crystal composition (B4) was applied to the vertically oriented film in a manner that the average film thickness of the coating film became 5 μm with the same width as the film, and heated and dried at 80°C for 1 minute, and then an ultraviolet irradiation device was used to irradiate ultraviolet rays from one side coated with the polymerizable liquid crystal composition (B4) (under a nitrogen atmosphere, the cumulative light amount at a wavelength of 365 nm: 500 mJ / cm 2), thereby obtaining a long film formed by a liquid crystal cured layer / vertical alignment film / substrate film. The average thickness X of the functional layer in the plane was confirmed to be 1 μm. In addition, the maximum height Y of the convex portion was 9 μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, there was no obvious adhesion in the surface and no detachment of the functional layer. The peelability and the like were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0525] 11. Comparative Example 1

[0526] A long film was obtained by the same method as in Example 1, except that the horizontal alignment film-forming composition (A1) and the polymerizable liquid crystal composition (B1) were applied to the cellulose triacetate film provided with the concavo-convex portion in the same manner as in Example 1 so as to have the width shown as the "functional layer coating width C" in Table 1. It should be noted that the horizontal alignment film-forming composition (A1) was applied so that the ends of the coating film of the horizontal alignment film-forming composition (A1) were located 25 mm inside from both ends of the substrate film, respectively, and the ends of the coating film did not cover the concavo-convex portions provided at both ends of the substrate film.

[0527] The average thickness X of the functional layer in the plane was confirmed to be 2 μm. In addition, the maximum height Y of the convex portion was 2 μm. The wound long film was stored in an environment of 23°C and 55% RH for 1 week and then unwound. As a result, adhesion occurred in the surface and deformation of the film roll was observed. In addition, the peelability evaluation of the functional layer showed that the end was torn into a serrated shape and fell off. The peelability and other evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0528] [Table 1]

[0529]

[0530] [Table 2]

[0531]

[0532] Description of Reference Numerals

[0533] 1: Base film

[0534] 2: Functional layer

[0535] 3: Concave and convex part

[0536] 11: Long strip film

[0537] A: Width of the short side of the substrate film

[0538] B1 and B2: Width of the short side of the concave-convex part

[0539] C: Width of the short side of the functional layer

Claims

1. A long film strip, comprising: A long strip-shaped substrate film having a concavo-convex portion at least at one end in the short side direction of at least one side; and A transferable functional layer comprising a cured layer of a polymerizable liquid crystal composition containing at least one polymerizable liquid crystal compound, in, The functional layer is laminated on the surface of the substrate film having the concavoconvex portion. The peeling force of the functional layer from the substrate film is greater than 0.02 N / 25 mm and less than 1 N / 25 mm, When the total width of the substrate film in the short side direction is A, the total width of the concave-convex portions of the substrate film in the short side direction is B, and the width of the functional layer in the short side direction is C, B+C>A is satisfied. The molecular alignment direction of the polymerizable liquid crystal compound in the cured layer constituting the functional layer is horizontal in-plane with respect to the longitudinal direction of the substrate film and is not parallel to the longitudinal direction of the substrate film.

2. The long film according to claim 1, wherein The substrate film is a cellulose-based resin film or an olefin-based resin film.

3. The long film according to claim 1 or 2, wherein: The relationship between the average thickness X of the functional layer in the plane and the maximum height Y of the convex part of the concavoconvex part satisfies 1.0 <Y / X≤15.0。 4. The long film according to claim 1 or 2, wherein: The cured product layer constituting the functional layer satisfies the following formulas (1) and (2): Re(450) / Re(550)≤1.00 (1) 100nm≤Re(550)≤150nm (2) In the formulas (1) and (2), Re(λ) represents the in-plane retardation value at a wavelength of λ nm.

5. The long film according to claim 1 or 2, wherein: The cured product layer constituting the functional layer satisfies the following formulas (3) and (4): 200nm≤Re(550)≤300nm (3) 1.00≤Re(450) / Re(550) (4) In the formulas (3) and (4), Re(λ) represents the in-plane phase difference value at a wavelength of λ nm.

6. The long film according to claim 1 or 2, wherein: The functional layer includes a photo-alignment film.

7. The long film according to claim 1 or 2, wherein: The molecular alignment direction of the polymerizable liquid crystal compound in the cured material layer constituting the functional layer is substantially vertical to the longitudinal direction of the substrate film in-plane.

8. The long film according to claim 1 or 2, wherein: The cured product layer constituting the functional layer satisfies the following formula (5): -150nm≤Rth(550)≤-20nm (5) In the formula (5), Rth(550) represents the phase difference value in the thickness direction of the cured layer at a wavelength of 550 nm.

Citation Information

Patent Citations

  • Acrylic film

    JP2007091784A

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Compound, optical film, and method for producing optical film

    JP2010031223A

  • compound

    JP2010270108A

  • Compound, optical film and method for producing optical film

    JP2011006360A